The RNA-binding protein tristetraprolin schedules apoptosis of pathogen-engaged neutrophils during bacterial infection - Ebner, Florian; Sedlyarov, Vitaly; Tasciyan, Saren; Ivin, Masa; Kratochvill, Franz; Gratz, Nina; Kenner, Lukas; Villunger, Andreas; Sixt, Michael K; Kovarik, Pavel (The Journal of Clinical Investigation)
Protective responses against pathogens require a rapid mobilization of resting neutrophils and the timely removal of activated ones. Neutrophils are exceptionally short-lived leukocytes, yet it remains unclear whether the lifespan of pathogen-engaged neutrophils is regulated differently from that in the circulating steady-state pool. Here, we have found that under homeostatic conditions, the mRNA-destabilizing protein tristetraprolin (TTP) regulates apoptosis and the numbers of activated infiltrating murine neutrophils but not neutrophil cellularity. Activated TTP-deficient neutrophils exhibited decreased apoptosis and enhanced accumulation at the infection site. In the context of myeloid-specific deletion of Ttp, the potentiation of neutrophil deployment protected mice against lethal soft tissue infection with Streptococcus pyogenes and prevented bacterial dissemination. Neutrophil transcriptome analysis revealed that decreased apoptosis of TTP-deficient neutrophils was specifically associated with elevated expression of myeloid cell leukemia 1 (Mcl1) but not other antiapoptotic B cell leukemia/ lymphoma 2 (Bcl2) family members. Higher Mcl1 expression resulted from stabilization of Mcl1 mRNA in the absence of TTP. The low apoptosis rate of infiltrating TTP-deficient neutrophils was comparable to that of transgenic Mcl1-overexpressing neutrophils. Our study demonstrates that posttranscriptional gene regulation by TTP schedules the termination of the antimicrobial engagement of neutrophils. The balancing role of TTP comes at the cost of an increased risk of bacterial infections.

Interstitial fluid osmolarity modulates the action of differential tissue surface tension in progenitor cell segregation during gastrulation - Krens, Gabriel; Veldhuis, Jim; Barone, Vanessa; Capek, Daniel; Maître, Jean-Léon; Brodland, Wayne; Heisenberg, Carl-Philipp J (Development)
The segregation of different cell types into distinct tissues is a fundamental process in metazoan development. Differences in cell adhesion and cortex tension are commonly thought to drive cell sorting by regulating tissue surface tension (TST). However, the role that differential TST plays in cell segregation within the developing embryo is as yet unclear. Here, we have analyzed the role of differential TST for germ layer progenitor cell segregation during zebrafish gastrulation. Contrary to previous observations that differential TST drives germ layer progenitor cell segregation in vitro, we show that germ layers display indistinguishable TST within the gastrulating embryo, arguing against differential TST driving germ layer progenitor cell segregation in vivo. We further show that the osmolarity of the interstitial fluid (IF) is an important factor that influences germ layer TST in vivo, and that lower osmolarity of the IF compared with standard cell culture medium can explain why germ layers display differential TST in culture but not in vivo. Finally, we show that directed migration of mesendoderm progenitors is required for germ layer progenitor cell segregation and germ layer formation.

Complex chromosomal neighborhood effects determine the adaptive potential of a gene under selection - Steinrück, Magdalena; Guet, Calin C (eLife)
How the organization of genes on a chromosome shapes adaptation is essential for understanding evolutionary paths. Here, we investigate how adaptation to rapidly increasing levels of antibiotic depends on the chromosomal neighborhood of a drug-resistance gene inserted at different positions of the Escherichia coli chromosome. Using a dual-fluorescence reporter that allows us to distinguish gene amplifications from other up-mutations, we track in real-time adaptive changes in expression of the drug-resistance gene. We find that the relative contribution of several mutation types differs systematically between loci due to properties of neighboring genes: essentiality, expression, orientation, termination, and presence of duplicates. These properties determine rate and fitness effects of gene amplification, deletions, and mutations compromising transcriptional termination. Thus, the adaptive potential of a gene under selection is a system-property with a complex genetic basis that is specific for each chromosomal locus, and it can be inferred from detailed functional and genomic data.

Stress induced mutagenesis: Stress diversity facilitates the persistence of mutator genes - Lukacisinova, Marta; Novak, Sebastian; Paixao, Tiago (PLoS Computational Biology)
Mutator strains are expected to evolve when the availability and effect of beneficial mutations are high enough to counteract the disadvantage from deleterious mutations that will inevitably accumulate. As the population becomes more adapted to its environment, both availability and effect of beneficial mutations necessarily decrease and mutation rates are predicted to decrease. It has been shown that certain molecular mechanisms can lead to increased mutation rates when the organism finds itself in a stressful environment. While this may be a correlated response to other functions, it could also be an adaptive mechanism, raising mutation rates only when it is most advantageous. Here, we use a mathematical model to investigate the plausibility of the adaptive hypothesis. We show that such a mechanism can be mantained if the population is subjected to diverse stresses. By simulating various antibiotic treatment schemes, we find that combination treatments can reduce the effectiveness of second-order selection on stress-induced mutagenesis. We discuss the implications of our results to strategies of antibiotic therapy.

Toward a quantitative understanding of antibiotic resistance evolution - Lukacisinova, Marta; Bollenbach, Mark Tobias (Current Opinion in Biotechnology)
The rising prevalence of antibiotic resistant bacteria is an increasingly serious public health challenge. To address this problem, recent work ranging from clinical studies to theoretical modeling has provided valuable insights into the mechanisms of resistance, its emergence and spread, and ways to counteract it. A deeper understanding of the underlying dynamics of resistance evolution will require a combination of experimental and theoretical expertise from different disciplines and new technology for studying evolution in the laboratory. Here, we review recent advances in the quantitative understanding of the mechanisms and evolution of antibiotic resistance. We focus on key theoretical concepts and new technology that enables well-controlled experiments. We further highlight key challenges that can be met in the near future to ultimately develop effective strategies for combating resistance.

Non-polynomial worst case analysis of recursive programs - Chatterjee, Krishnendu; Fu, Hongfei; Goharshady, Amir
We study the problem of developing efficient approaches for proving worst-case bounds of non-deterministic recursive programs. Ranking functions are sound and complete for proving termination and worst-case bounds of non-recursive programs. First, we apply ranking functions to recursion, resulting in measure functions, and show that they provide a sound and complete approach to prove worst-case bounds of non-deterministic recursive programs. Our second contribution is the synthesis of measure functions in non-polynomial forms. We show that non-polynomial measure functions with logarithm and exponentiation can be synthesized through abstraction of logarithmic or exponentiation terms, Farkas’ Lemma, and Handelman’s Theorem using linear programming. While previous methods obtain worst-case polynomial bounds, our approach can synthesize bounds of the form O(n log n) as well as O(nr) where r is not an integer. We present experimental results to demonstrate that our approach can efficiently obtain worst-case bounds of classical recursive algorithms such as Merge-Sort, Closest-Pair, Karatsuba’s algorithm and Strassen’s algorithm.

JTDec: A tool for tree decompositions in soot - Chatterjee, Krishnendu; Goharshady, Amir; Pavlogiannis, Andreas
The notion of treewidth of graphs has been exploited for faster algorithms for several problems arising in verification and program analysis. Moreover, various notions of balanced tree decompositions have been used for improved algorithms supporting dynamic updates and analysis of concurrent programs. In this work, we present a tool for constructing tree-decompositions of CFGs obtained from Java methods, which is implemented as an extension to the widely used Soot framework. The experimental results show that our implementation on real-world Java benchmarks is very efficient. Our tool also provides the first implementation for balancing tree-decompositions. In summary, we present the first tool support for exploiting treewidth in the static analysis problems on Java programs.

Friction forces position the neural anlage - Smutny, Michael; Ákos, Zsuzsa; Grigolon, Silvia; Shamipour, Shayan; Ruprecht, Verena; Capek, Daniel; Behrndt, Martin; Papusheva, Ekaterina; Tada, Masazumi; Hof, Björn; Vicsek, Tamás; Salbreux, Guillaume; et al. (Nature Cell Biology)
During embryonic development, mechanical forces are essential for cellular rearrangements driving tissue morphogenesis. Here, we show that in the early zebrafish embryo, friction forces are generated at the interface between anterior axial mesoderm (prechordal plate, ppl) progenitors migrating towards the animal pole and neurectoderm progenitors moving in the opposite direction towards the vegetal pole of the embryo. These friction forces lead to global rearrangement of cells within the neurectoderm and determine the position of the neural anlage. Using a combination of experiments and simulations, we show that this process depends on hydrodynamic coupling between neurectoderm and ppl as a result of E-cadherin-mediated adhesion between those tissues. Our data thus establish the emergence of friction forces at the interface between moving tissues as a critical force-generating process shaping the embryo.

An effective feedback loop between cell-cell contact duration and morphogen signaling determines cell fate - Barone, Vanessa; Lang, Moritz; Krens, Gabriel; Pradhan, Saurabh; Shamipour, Shayan; Sako, Keisuke; Sikora, Mateusz K; Guet, Calin C; Heisenberg, Carl-Philipp J (Developmental Cell)
Cell-cell contact formation constitutes an essential step in evolution, leading to the differentiation of specialized cell types. However, remarkably little is known about whether and how the interplay between contact formation and fate specification affects development. Here, we identify a positive feedback loop between cell-cell contact duration, morphogen signaling, and mesendoderm cell-fate specification during zebrafish gastrulation. We show that long-lasting cell-cell contacts enhance the competence of prechordal plate (ppl) progenitor cells to respond to Nodal signaling, required for ppl cell-fate specification. We further show that Nodal signaling promotes ppl cell-cell contact duration, generating a positive feedback loop between ppl cell-cell contact duration and cell-fate specification. Finally, by combining mathematical modeling and experimentation, we show that this feedback determines whether anterior axial mesendoderm cells become ppl or, instead, turn into endoderm. Thus, the interdependent activities of cell-cell signaling and contact formation control fate diversification within the developing embryo.

Cell polarity in cerebral cortex development - cellular architecture shaped by biochemical networks - Hansen, Andi H; Düllberg, Christian F; Mieck, Christine; Loose, Martin; Hippenmeyer, Simon (Frontiers in Cellular Neuroscience)
The human cerebral cortex is the seat of our cognitive abilities and composed of an extraordinary number of neurons, organized in six distinct layers. The establishment of specific morphological and physiological features in individual neurons needs to be regulated with high precision. Impairments in the sequential developmental programs instructing corticogenesis lead to alterations in the cortical cytoarchitecture which is thought to represent the major underlying cause for several neurological disorders including neurodevelopmental and psychiatric diseases. In this review we discuss the role of cell polarity at sequential stages during cortex development. We first provide an overview of morphological cell polarity features in cortical neural stem cells and newly-born postmitotic neurons. We then synthesize a conceptual molecular and biochemical framework how cell polarity is established at the cellular level through a break in symmetry in nascent cortical projection neurons. Lastly we provide a perspective how the molecular mechanisms applying to single cells could be probed and integrated in an in vivo and tissue-wide context.

An orthogonal permease–inducer–repressor feedback loop shows bistability - Gnügge, Robert; Dharmarajan, Lekshmi; Lang, Moritz; Stelling, Jörg (ACS Synthetic Biology)
Feedback loops in biological networks, among others, enable differentiation and cell cycle progression, and increase robustness in signal transduction. In natural networks, feedback loops are often complex and intertwined, making it challenging to identify which loops are mainly responsible for an observed behavior. However, minimal synthetic replicas could allow for such identification. Here, we engineered a synthetic permease-inducer-repressor system in Saccharomyces cerevisiae to analyze if a transport-mediated positive feedback loop could be a core mechanism for the switch-like behavior in the regulation of metabolic gene networks such as the S. cerevisiae GAL system or the Escherichia coli lac operon. We characterized the synthetic circuit using deterministic and stochastic mathematical models. Similar to its natural counterparts, our synthetic system shows bistable and hysteretic behavior, and the inducer concentration range for bistability as well as the switching rates between the two stable states depend on the repressor concentration. Our results indicate that a generic permease–inducer–repressor circuit with a single feedback loop is sufficient to explain the experimentally observed bistable behavior of the natural systems. We anticipate that the approach of reimplementing natural systems with orthogonal parts to identify crucial network components is applicable to other natural systems such as signaling pathways.

Conditionally optimal algorithms for generalized Büchi Games - Chatterjee, Krishnendu; Dvorák, Wolfgang; Henzinger, Monika H; Loitzenbauer, Veronika
Games on graphs provide the appropriate framework to study several central problems in computer science, such as verification and synthesis of reactive systems. One of the most basic objectives for games on graphs is the liveness (or Büchi) objective that given a target set of vertices requires that some vertex in the target set is visited infinitely often. We study generalized Büchi objectives (i.e., conjunction of liveness objectives), and implications between two generalized Büchi objectives (known as GR(1) objectives), that arise in numerous applications in computer-aided verification. We present improved algorithms and conditional super-linear lower bounds based on widely believed assumptions about the complexity of (A1) combinatorial Boolean matrix multiplication and (A2) CNF-SAT. We consider graph games with n vertices, m edges, and generalized Büchi objectives with k conjunctions. First, we present an algorithm with running time O(k*n^2), improving the previously known O(k*n*m) and O(k^2*n^2) worst-case bounds. Our algorithm is optimal for dense graphs under (A1). Second, we show that the basic algorithm for the problem is optimal for sparse graphs when the target sets have constant size under (A2). Finally, we consider GR(1) objectives, with k_1 conjunctions in the antecedent and k_2 conjunctions in the consequent, and present an O(k_1 k_2 n^{2.5})-time algorithm, improving the previously known O(k_1*k_2*n*m)-time algorithm for m > n^{1.5}.

On the skolem problem for continuous linear dynamical systems - Chonev, Ventsislav K; Ouaknine, Joël; Worrell, James
The Continuous Skolem Problem asks whether a real-valued function satisfying a linear differen- tial equation has a zero in a given interval of real numbers. This is a fundamental reachability problem for continuous linear dynamical systems, such as linear hybrid automata and continuous- time Markov chains. Decidability of the problem is currently open – indeed decidability is open even for the sub-problem in which a zero is sought in a bounded interval. In this paper we show decidability of the bounded problem subject to Schanuel’s Conjecture, a unifying conjecture in transcendental number theory. We furthermore analyse the unbounded problem in terms of the frequencies of the differential equation, that is, the imaginary parts of the characteristic roots. We show that the unbounded problem can be reduced to the bounded problem if there is at most one rationally linearly independent frequency, or if there are two rationally linearly independent frequencies and all characteristic roots are simple. We complete the picture by showing that de- cidability of the unbounded problem in the case of two (or more) rationally linearly independent frequencies would entail a major new effectiveness result in Diophantine approximation, namely computability of the Diophantine-approximation types of all real algebraic numbers.

Computation tree logic for synchronization properties - Chatterjee, Krishnendu; Doyen, Laurent
We present a logic that extends CTL (Computation Tree Logic) with operators that express synchronization properties. A property is synchronized in a system if it holds in all paths of a certain length. The new logic is obtained by using the same path quantifiers and temporal operators as in CTL, but allowing a different order of the quantifiers. This small syntactic variation induces a logic that can express non-regular properties for which known extensions of MSO with equality of path length are undecidable. We show that our variant of CTL is decidable and that the model-checking problem is in Delta_3^P = P^{NP^NP}, and is DP-hard. We analogously consider quantifier exchange in extensions of CTL, and we present operators defined using basic operators of CTL* that express the occurrence of infinitely many synchronization points. We show that the model-checking problem remains in Delta_3^P. The distinguishing power of CTL and of our new logic coincide if the Next operator is allowed in the logics, thus the classical bisimulation quotient can be used for state-space reduction before model checking.

Cellular mechanisms for cargo delivery and polarity maintenance at different polar domains in plant cells - Łangowski, Łukasz; Wabnik, Krzysztof T; Li, Hongjiang; Vanneste, Steffen; Naramoto, Satoshi; Tanaka, Hirokazu; Friml, Jirí (Cell Discovery)
The asymmetric localization of proteins in the plasma membrane domains of eukaryotic cells is a fundamental manifestation of cell polarity that is central to multicellular organization and developmental patterning. In plants, the mechanisms underlying the polar localization of cargo proteins are still largely unknown and appear to be fundamentally distinct from those operating in mammals. Here, we present a systematic, quantitative comparative analysis of the polar delivery and subcellular localization of proteins that characterize distinct polar plasma membrane domains in plant cells. The combination of microscopic analyses and computational modeling revealed a mechanistic framework common to diverse polar cargos and underlying the establishment and maintenance of apical, basal, and lateral polar domains in plant cells. This mechanism depends on the polar secretion, constitutive endocytic recycling, and restricted lateral diffusion of cargos within the plasma membrane. Moreover, our observations suggest that polar cargo distribution involves the individual protein potential to form clusters within the plasma membrane and interact with the extracellular matrix. Our observations provide insights into the shared cellular mechanisms of polar cargo delivery and polarity maintenance in plant cells.

Relevant sparse codes with variational information bottleneck - Chalk, Matthew J; Marre, Olivier; Tkacik, Gasper
In many applications, it is desirable to extract only the relevant aspects of data. A principled way to do this is the information bottleneck (IB) method, where one seeks a code that maximises information about a relevance variable, Y, while constraining the information encoded about the original data, X. Unfortunately however, the IB method is computationally demanding when data are high-dimensional and/or non-gaussian. Here we propose an approximate variational scheme for maximising a lower bound on the IB objective, analogous to variational EM. Using this method, we derive an IB algorithm to recover features that are both relevant and sparse. Finally, we demonstrate how kernelised versions of the algorithm can be used to address a broad range of problems with non-linear relation between X and Y.

KCTD12 auxiliary proteins modulate kinetics of GABAB receptor-mediated inhibition in Cholecystokinin-containing interneurons - Booker, Sam; Althof, Daniel; Gross, Anna; Loreth, Desiree; Müller, Johanna; Unger, Andreas; Fakler, Bernd; Varro, Andrea; Watanabe, Masahiko; Gassmann, Martin; Bettler, Bernhard; Shigemoto, Ryuichi; et al. (Cerebral Cortex)
Cholecystokinin-expressing interneurons (CCK-INs) mediate behavior state-dependent inhibition in cortical circuits and themselves receive strong GABAergic input. However, it remains unclear to what extent GABABreceptors (GABABRs) contribute to their inhibitory control. Using immunoelectron microscopy, we found that CCK-INs in the rat hippocampus possessed high levels of dendritic GABABRs and KCTD12 auxiliary proteins, whereas postsynaptic effector Kir3 channels were present at lower levels. Consistently, whole-cell recordings revealed slow GABABR-mediated inhibitory postsynaptic currents (IPSCs) in most CCK-INs. In spite of the higher surface density of GABABRs in CCK-INs than in CA1 principal cells, the amplitudes of IPSCs were comparable, suggesting that the expression of Kir3 channels is the limiting factor for the GABABR currents in these INs. Morphological analysis showed that CCK-INs were diverse, comprising perisomatic-targeting basket cells (BCs), as well as dendrite-targeting (DT) interneurons, including a previously undescribed DT type. GABABR-mediated IPSCs in CCK-INs were large in BCs, but small in DT subtypes. In response to prolonged activation, GABABR-mediated currents displayed strong desensitization, which was absent in KCTD12-deficient mice. This study highlights that GABABRs differentially control CCK-IN subtypes, and the kinetics and desensitization of GABABR-mediated currents are modulated by KCTD12 proteins.

Nested weighted limit-average automata of bounded width - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan
While weighted automata provide a natural framework to express quantitative properties, many basic properties like average response time cannot be expressed with weighted automata. Nested weighted automata extend weighted automata and consist of a master automaton and a set of slave automata that are invoked by the master automaton. Nested weighted automata are strictly more expressive than weighted automata (e.g., average response time can be expressed with nested weighted automata), but the basic decision questions have higher complexity (e.g., for deterministic automata, the emptiness question for nested weighted automata is PSPACE-hard, whereas the corresponding complexity for weighted automata is PTIME). We consider a natural subclass of nested weighted automata where at any point at most a bounded number k of slave automata can be active. We focus on automata whose master value function is the limit average. We show that these nested weighted automata with bounded width are strictly more expressive than weighted automata (e.g., average response time with no overlapping requests can be expressed with bound k=1, but not with non-nested weighted automata). We show that the complexity of the basic decision problems (i.e., emptiness and universality) for the subclass with k constant matches the complexity for weighted automata. Moreover, when k is part of the input given in unary we establish PSPACE-completeness.

Local linearizability for concurrent container-type data structures - Haas, Andreas; Henzinger, Thomas A; Holzer, Andreas; Kirsch, Christoph; Lippautz, Michael; Payer, Hannes; Sezgin, Ali; Sokolova, Ana; Veith, Helmut (Leibniz International Proceedings in Informatics)
The semantics of concurrent data structures is usually given by a sequential specification and a consistency condition. Linearizability is the most popular consistency condition due to its simplicity and general applicability. Nevertheless, for applications that do not require all guarantees offered by linearizability, recent research has focused on improving performance and scalability of concurrent data structures by relaxing their semantics. In this paper, we present local linearizability, a relaxed consistency condition that is applicable to container-type concurrent data structures like pools, queues, and stacks. While linearizability requires that the effect of each operation is observed by all threads at the same time, local linearizability only requires that for each thread T, the effects of its local insertion operations and the effects of those removal operations that remove values inserted by T are observed by all threads at the same time. We investigate theoretical and practical properties of local linearizability and its relationship to many existing consistency conditions. We present a generic implementation method for locally linearizable data structures that uses existing linearizable data structures as building blocks. Our implementations show performance and scalability improvements over the original building blocks and outperform the fastest existing container-type implementations.

Computational multicopter design - Du, Tao; Schulz, Adriana; Zhu, Bo; Bickel, Bernd; Matusik, Wojciech
We present an interactive system for computational design, optimization, and fabrication of multicopters. Our computational approach allows non-experts to design, explore, and evaluate a wide range of different multicopters. We provide users with an intuitive interface for assembling a multicopter from a collection of components (e.g., propellers, motors, and carbon fiber rods). Our algorithm interactively optimizes shape and controller parameters of the current design to ensure its proper operation. In addition, we allow incorporating a variety of other metrics (such as payload, battery usage, size, and cost) into the design process and exploring tradeoffs between them. We show the efficacy of our method and system by designing, optimizing, fabricating, and operating multicopters with complex geometries and propeller configurations. We also demonstrate the ability of our optimization algorithm to improve the multicopter performance under different metrics.

Lifelong learning with weighted majority votes - Pentina, Anastasia; Urner, Ruth
Better understanding of the potential benefits of information transfer and representation learning is an important step towards the goal of building intelligent systems that are able to persist in the world and learn over time. In this work, we consider a setting where the learner encounters a stream of tasks but is able to retain only limited information from each encountered task, such as a learned predictor. In contrast to most previous works analyzing this scenario, we do not make any distributional assumptions on the task generating process. Instead, we formulate a complexity measure that captures the diversity of the observed tasks. We provide a lifelong learning algorithm with error guarantees for every observed task (rather than on average). We show sample complexity reductions in comparison to solving every task in isolation in terms of our task complexity measure. Further, our algorithmic framework can naturally be viewed as learning a representation from encountered tasks with a neural network.

FlexMolds: Automatic design of flexible shells for molding - Malomo, Luigi; Pietroni, Nico; Bickel, Bernd; Cignoni, Paolo
We present FlexMolds, a novel computational approach to automatically design flexible, reusable molds that, once 3D printed, allow us to physically fabricate, by means of liquid casting, multiple copies of complex shapes with rich surface details and complex topology. The approach to design such flexible molds is based on a greedy bottom-up search of possible cuts over an object, evaluating for each possible cut the feasibility of the resulting mold. We use a dynamic simulation approach to evaluate candidate molds, providing a heuristic to generate forces that are able to open, detach, and remove a complex mold from the object it surrounds. We have tested the approach with a number of objects with nontrivial shapes and topologies.

Improving weakly-supervised object localization by micro-annotation - Kolesnikov, Alexander; Lampert, Christoph (Proceedings of the British Machine Vision Conference 2016)
Weakly-supervised object localization methods tend to fail for object classes that consistently co-occur with the same background elements, e.g. trains on tracks. We propose a method to overcome these failures by adding a very small amount of model-specific additional annotation. The main idea is to cluster a deep network\'s mid-level representations and assign object or distractor labels to each cluster. Experiments show substantially improved localization results on the challenging ILSVC2014 dataset for bounding box detection and the PASCAL VOC2012 dataset for semantic segmentation.

Parallel reachability analysis for hybrid systems - Gurung, Amit; Deka, Arup; Bartocci, Ezio; Bogomolov, Sergiy; Grosu, Radu; Ray, Rajarshi
We propose two parallel state-space-exploration algorithms for hybrid automaton (HA), with the goal of enhancing performance on multi-core shared-memory systems. The first uses the parallel, breadth-first-search algorithm (PBFS) of the SPIN model checker, when traversing the discrete modes of the HA, and enhances it with a parallel exploration of the continuous states within each mode. We show that this simple-minded extension of PBFS does not provide the desired load balancing in many HA benchmarks. The second algorithm is a task-parallel BFS algorithm (TP-BFS), which uses a cheap precomputation of the cost associated with the post operations (both continuous and discrete) in order to improve load balancing. We illustrate the TP-BFS and the cost precomputation of the post operators on a support-function-based algorithm for state-space exploration. The performance comparison of the two algorithms shows that, in general, TP-BFS provides a better utilization/load-balancing of the CPU. Both algorithms are implemented in the model checker XSpeed. Our experiments show a maximum speed-up of more than 2000 χ on a navigation benchmark, with respect to SpaceEx LGG scenario. In order to make the comparison fair, we employed an equal number of post operations in both tools. To the best of our knowledge, this paper represents the first attempt to provide parallel, reachability-analysis algorithms for HA.

Estimating nonlinear neural response functions using GP priors and Kronecker methods - Savin, Cristina; Tkacik, Gasper
Jointly characterizing neural responses in terms of several external variables promises novel insights into circuit function, but remains computationally prohibitive in practice. Here we use gaussian process (GP) priors and exploit recent advances in fast GP inference and learning based on Kronecker methods, to efficiently estimate multidimensional nonlinear tuning functions. Our estimator require considerably less data than traditional methods and further provides principled uncertainty estimates. We apply these tools to hippocampal recordings during open field exploration and use them to characterize the joint dependence of CA1 responses on the position of the animal and several other variables, including the animal\'s speed, direction of motion, and network oscillations.Our results provide an unprecedentedly detailed quantification of the tuning of hippocampal neurons. The model\'s generality suggests that our approach can be used to estimate neural response properties in other brain regions.

Efficient single sideband microwave to optical conversion using a LiNbO₃ WGM-resonator - Rueda, Alfredo; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Georg; Strekalov, Dimitry; Marquardt, Christoph; Fink, Johannes M; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald
We present a coherent microwave to telecom signal converter based on the electro-optical effect using a crystalline WGM-resonator coupled to a 3D microwave cavity, achieving high photon conversion efficiency of 0.1% with MHz bandwidth.

Synthesizing time triggered schedules for switched networks with faulty links - Avni, Guy; Guha, Shibashis; Rodríguez Navas, Guillermo (Proceedings of the 13th International Conference on Embedded Software)
Time-triggered (TT) switched networks are a deterministic communication infrastructure used by real-time distributed embedded systems. These networks rely on the notion of globally discretized time (i.e. time slots) and a static TT schedule that prescribes which message is sent through which link at every time slot, such that all messages reach their destination before a global timeout. These schedules are generated offline, assuming a static network with fault-free links, and entrusting all error-handling functions to the end user. Assuming the network is static is an over-optimistic view, and indeed links tend to fail in practice. We study synthesis of TT schedules on a network in which links fail over time and we assume the switches run a very simple error-recovery protocol once they detect a crashed link. We address the problem of finding a pk; qresistant schedule; namely, one that, assuming the switches run a fixed error-recovery protocol, guarantees that the number of messages that arrive at their destination by the timeout is at least no matter what sequence of at most k links fail. Thus, we maintain the simplicity of the switches while giving a guarantee on the number of messages that meet the timeout. We show how a pk; q-resistant schedule can be obtained using a CEGAR-like approach: find a schedule, decide whether it is pk; q-resistant, and if it is not, use the witnessing fault sequence to generate a constraint that is added to the program. The newly added constraint disallows the schedule to be regenerated in a future iteration while also eliminating several other schedules that are not pk; q-resistant. We illustrate the applicability of our approach using an SMT-based implementation. © 2016 ACM.

Tutorial: Software tools for hybrid systems verification transformation and synthesis C2E2 HyST and TuLiP - Duggirala, Parasara; Fan, Chuchu; Potok, Matthew; Qi, Bolun; Mitra, Sayan; Viswanathan, Mahesh; Bak, Stanley; Bogomolov, Sergiy; Johnson, Taylor; Nguyen, Luan; Schilling, Christian; Sogokon, Andrew; et al. (2016 IEEE Conference on Control Applications)
Hybrid systems have both continuous and discrete dynamics and are useful for modeling a variety of control systems, from air traffic control protocols to robotic maneuvers and beyond. Recently, numerous powerful and scalable tools for analyzing hybrid systems have emerged. Several of these tools implement automated formal methods for mathematically proving a system meets a specification. This tutorial session will present three recent hybrid systems tools: C2E2, HyST, and TuLiP. C2E2 is a simulated-based verification tool for hybrid systems, and uses validated numerical solvers and bloating of simulation traces to verify systems meet specifications. HyST is a hybrid systems model transformation and translation tool, and uses a canonical intermediate representation to support most of the recent verification tools, as well as automated sound abstractions that simplify verification of a given hybrid system. TuLiP is a controller synthesis tool for hybrid systems, where given a temporal logic specification to be satisfied for a system (plant) model, TuLiP will find a controller that meets a given specification. © 2016 IEEE.

Space-time sculpting of liquid animation - Manteaux, Pierre; Vimont, Ulysse; Wojtan, Christopher J; Rohmer, Damien; Cani, Marie (Proceedings of the 9th International Conference on Motion in Games)
We propose an interactive sculpting system for seamlessly editing pre-computed animations of liquid, without the need for any resimulation. The input is a sequence of meshes without correspondences representing the liquid surface over time. Our method enables the efficient selection of consistent space-time parts of this animation, such as moving waves or droplets, which we call space-time features. Once selected, a feature can be copied, edited, or duplicated and then pasted back anywhere in space and time in the same or in another liquid animation sequence. Our method circumvents tedious user interactions by automatically computing the spatial and temporal ranges of the selected feature. We also provide space-time shape editing tools for non-uniform scaling, rotation, trajectory changes, and temporal editing to locally speed up or slow down motion. Using our tools, the user can edit and progressively refine any input simulation result, possibly using a library of precomputed space-time features extracted from other animations. In contrast to the trial-and-error loop usually required to edit animation results through the tuning of indirect simulation parameters, our method gives the user full control over the edited space-time behaviors. © 2016 Copyright held by the owner/author(s).

RASGRP1 deficiency causes immunodeficiency with impaired cytoskeletal dynamics - Salzer, Elisabeth; Çaǧdaş, Deniz; Hons, Miroslav; Mace, Emily; Garncarz, Wojciech; Petronczki, Oezlem; Platzer, René; Pfajfer, Laurène; Bilic, Ivan; Ban, Sol; Willmann, Katharina; Mukherjee, Malini; et al. (Nature Immunology)
RASGRP1 is an important guanine nucleotide exchange factor and activator of the RAS-MAPK pathway following T cell antigen receptor (TCR) signaling. The consequences of RASGRP1 mutations in humans are unknown. In a patient with recurrent bacterial and viral infections, born to healthy consanguineous parents, we used homozygosity mapping and exome sequencing to identify a biallelic stop-gain variant in RASGRP1. This variant segregated perfectly with the disease and has not been reported in genetic databases. RASGRP1 deficiency was associated in T cells and B cells with decreased phosphorylation of the extracellular-signal-regulated serine kinase ERK, which was restored following expression of wild-type RASGRP1. RASGRP1 deficiency also resulted in defective proliferation, activation and motility of T cells and B cells. RASGRP1-deficient natural killer (NK) cells exhibited impaired cytotoxicity with defective granule convergence and actin accumulation. Interaction proteomics identified the dynein light chain DYNLL1 as interacting with RASGRP1, which links RASGRP1 to cytoskeletal dynamics. RASGRP1-deficient cells showed decreased activation of the GTPase RhoA. Treatment with lenalidomide increased RhoA activity and reversed the migration and activation defects of RASGRP1-deficient lymphocytes.

Quantitative automata under probabilistic semantics - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (Proceedings of the 31st Annual ACM/IEEE Symposium)
Automata with monitor counters, where the transitions do not depend on counter values, and nested weighted automata are two expressive automata-theoretic frameworks for quantitative properties. For a well-studied and wide class of quantitative functions, we establish that automata with monitor counters and nested weighted automata are equivalent. We study for the first time such quantitative automata under probabilistic semantics. We show that several problems that are undecidable for the classical questions of emptiness and universality become decidable under the probabilistic semantics. We present a complete picture of decidability for such automata, and even an almost-complete picture of computational complexity, for the probabilistic questions we consider. © 2016 ACM.

Model and objective separation with conditional lower bounds: disjunction is harder than conjunction - Chatterjee, Krishnendu; Dvoák, Wolfgang; Henzinger, Monika H; Loitzenbauer, Veronika (Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science)
Given a model of a system and an objective, the model-checking question asks whether the model satisfies the objective. We study polynomial-time problems in two classical models, graphs and Markov Decision Processes (MDPs), with respect to several fundamental -regular objectives, e.g., Rabin and Streett objectives. For many of these problems the best-known upper bounds are quadratic or cubic, yet no super-linear lower bounds are known. In this work our contributions are two-fold: First, we present several improved algorithms, and second, we present the first conditional super-linear lower bounds based on widely believed assumptions about the complexity of CNF-SAT and combinatorial Boolean matrix multiplication. A separation result for two models with respect to an objective means a conditional lower bound for one model that is strictly higher than the existing upper bound for the other model, and similarly for two objectives with respect to a model. Our results establish the following separation results: (1) A separation of models (graphs and MDPs) for disjunctive queries of reachability and Büchi objectives. (2) Two kinds of separations of objectives, both for graphs and MDPs, namely, (2a) the separation of dual objectives such as Streett/Rabin objectives, and (2b) the separation of conjunction and disjunction of multiple objectives of the same type such as safety, Büchi, and coBüchi. In summary, our results establish the first model and objective separation results for graphs and MDPs for various classical -regular objectives. Quite strikingly, we establish conditional lower bounds for the disjunction of objectives that are strictly higher than the existing upper bounds for the conjunction of the same objectives. © 2016 ACM.

Heme drives hemolysis-induced susceptibility to infection via disruption of phagocyte functions - Martins, Rui; Maier, Julia; Gorki, Anna; Huber, Kilian; Sharif, Omar; Starkl, Philipp; Saluzzo, Simona; Quattrone, Federica; Gawish, Riem; Lakovits, Karin; Aichinger, Michael; Radic Sarikas, Branka; et al. (Nature Immunology)
Hemolysis drives susceptibility to bacterial infections and predicts poor outcome from sepsis. These detrimental effects are commonly considered to be a consequence of heme-iron serving as a nutrient for bacteria. We employed a Gram-negative sepsis model and found that elevated heme levels impaired the control of bacterial proliferation independently of heme-iron acquisition by pathogens. Heme strongly inhibited phagocytosis and the migration of human and mouse phagocytes by disrupting actin cytoskeletal dynamics via activation of the GTP-binding Rho family protein Cdc42 by the guanine nucleotide exchange factor DOCK8. A chemical screening approach revealed that quinine effectively prevented heme effects on the cytoskeleton, restored phagocytosis and improved survival in sepsis. These mechanistic insights provide potential therapeutic targets for patients with sepsis or hemolytic disorders.

Hierarchic genetic strategy with maturing as a generic tool for multiobjective optimization - Łazarz, Radosław; Idzik, Michał; Gądek, Konrad; Gajda-Zagorska, Ewa P (Journal of Computational Science)
In this paper we introduce the Multiobjective Optimization Hierarchic Genetic Strategy with maturing (MO-mHGS), a meta-algorithm that performs evolutionary optimization in a hierarchy of populations. The maturing mechanism improves growth and reduces redundancy. The performance of MO-mHGS with selected state-of-the-art multiobjective evolutionary algorithms as internal algorithms is analysed on benchmark problems and their modifications for which single fitness evaluation time depends on the solution accuracy. We compare the proposed algorithm with the Island Model Genetic Algorithm as well as with single-deme methods, and discuss the impact of internal algorithms on the MO-mHGS meta-algorithm. © 2016 Elsevier B.V.

Ground states of large bosonic systems: The gross Pitaevskii limit revisited - Nam, Phan; Rougerie, Nicolas; Seiringer, Robert (Analysis and PDE)
We study the ground state of a dilute Bose gas in a scaling limit where the Gross-Pitaevskii functional emerges. This is a repulsive nonlinear Schrödinger functional whose quartic term is proportional to the scattering length of the interparticle interaction potential. We propose a new derivation of this limit problem, with a method that bypasses some of the technical difficulties that previous derivations had to face. The new method is based on a combination of Dyson\'s lemma, the quantum de Finetti theorem and a second moment estimate for ground states of the effective Dyson Hamiltonian. It applies equally well to the case where magnetic fields or rotation are present.

Enquiry into the topology of plasma membrane localized PIN auxin transport components - Nodzyński, Tomasz; Vanneste, Steffen; Zwiewka, Marta; Pernisová, Markéta; Hejátko, Jan; Friml, Jirí (Molecular Plant)
Auxin directs plant ontogenesis via differential accumulation within tissues depending largely on the activity of PIN proteins that mediate auxin efflux from cells and its directional cell-to-cell transport. Regardless of the developmental importance of PINs, the structure of these transporters is poorly characterized. Here, we present experimental data concerning protein topology of plasma membrane-localized PINs. Utilizing approaches based on pH-dependent quenching of fluorescent reporters combined with immunolocalization techniques, we mapped the membrane topology of PINs and further cross-validated our results using available topology modeling software. We delineated the topology of PIN1 with two transmembrane (TM) bundles of five α-helices linked by a large intracellular loop and a C-terminus positioned outside the cytoplasm. Using constraints derived from our experimental data, we also provide an updated position of helical regions generating a verisimilitude model of PIN1. Since the canonical long PINs show a high degree of conservation in TM domains and auxin transport capacity has been demonstrated for Arabidopsis representatives of this group, this empirically enhanced topological model of PIN1 will be an important starting point for further studies on PIN structure–function relationships. In addition, we have established protocols that can be used to probe the topology of other plasma membrane proteins in plants. © 2016 The Authors

Auxin flow mediated competition between axillary buds to restore apical dominance - Balla, Jozef; Medved'Ová, Zuzana; Kalousek, Petr; Matiješčuková, Natálie; Friml, Jirí; Reinöhl, Vilém; Procházka, Stanislav (Scientific Reports)
Apical dominance is one of the fundamental developmental phenomena in plant biology, which determines the overall architecture of aerial plant parts. Here we show apex decapitation activated competition for dominance in adjacent upper and lower axillary buds. A two-nodal-bud pea (Pisum sativum L.) was used as a model system to monitor and assess auxin flow, auxin transport channels, and dormancy and initiation status of axillary buds. Auxin flow was manipulated by lateral stem wounds or chemically by auxin efflux inhibitors 2,3,5-triiodobenzoic acid (TIBA), 1-N-naphtylphtalamic acid (NPA), or protein synthesis inhibitor cycloheximide (CHX) treatments, which served to interfere with axillary bud competition. Redirecting auxin flow to different points influenced which bud formed the outgrowing and dominant shoot. The obtained results proved that competition between upper and lower axillary buds as secondary auxin sources is based on the same auxin canalization principle that operates between the shoot apex and axillary bud. © The Author(s) 2016.

A study of rigorous ODE integrators for multi scale set oriented computations - Miyaji, Tomoyuki; Pilarczyk, Pawel; Gameiro, Marcio; Kokubu, Hiroshi; Mischaikow, Konstantin (Applied Numerical Mathematics)
We study the usefulness of two most prominent publicly available rigorous ODE integrators: one provided by the CAPD group (capd.ii.uj.edu.pl), the other based on the COSY Infinity project (cosyinfinity.org). Both integrators are capable of handling entire sets of initial conditions and provide tight rigorous outer enclosures of the images under a time-T map. We conduct extensive benchmark computations using the well-known Lorenz system, and compare the computation time against the final accuracy achieved. We also discuss the effect of a few technical parameters, such as the order of the numerical integration method, the value of T, and the phase space resolution. We conclude that COSY may provide more precise results due to its ability of avoiding the variable dependency problem. However, the overall cost of computations conducted using CAPD is typically lower, especially when intervals of parameters are involved. Moreover, access to COSY is limited (registration required) and the rigorous ODE integrators are not publicly available, while CAPD is an open source free software project. Therefore, we recommend the latter integrator for this kind of computations. Nevertheless, proper choice of the various integration parameters turns out to be of even greater importance than the choice of the integrator itself. © 2016 IMACS. Published by Elsevier B.V. All rights reserved.

A Radical Break Restraining Neutrophil Migration - Renkawitz, Jörg; Sixt, Michael K (Developmental Cell)
When neutrophils infiltrate a site of inflammation, they have to stop at the right place to exert their effector function. In this issue of Developmental Cell, Wang et al. (2016) show that neutrophils sense reactive oxygen species via the TRPM2 channel to arrest migration at their target site. © 2016 Elsevier Inc.

A noncanonical auxin sensing mechanism is required for organ morphogenesis in arabidopsis - Simonini, Sara; Deb, Joyita; Moubayidin, Laila; Stephenson, Pauline; Valluru, Manoj; Freire Rios, Alejandra; Sorefan, Karim; Weijers, Dolf; Friml, Jirí; Östergaard, Lars (Genes and Development)
Tissue patterning in multicellular organisms is the output of precise spatio–temporal regulation of gene expression coupled with changes in hormone dynamics. In plants, the hormone auxin regulates growth and development at every stage of a plant’s life cycle. Auxin signaling occurs through binding of the auxin molecule to a TIR1/AFB F-box ubiquitin ligase, allowing interaction with Aux/IAA transcriptional repressor proteins. These are subsequently ubiquitinated and degraded via the 26S proteasome, leading to derepression of auxin response factors (ARFs). How auxin is able to elicit such a diverse range of developmental responses through a single signaling module has not yet been resolved. Here we present an alternative auxin-sensing mechanism in which the ARF ARF3/ETTIN controls gene expression through interactions with process-specific transcription factors. This noncanonical hormonesensing mechanism exhibits strong preference for the naturally occurring auxin indole 3-acetic acid (IAA) and is important for coordinating growth and patterning in diverse developmental contexts such as gynoecium morphogenesis, lateral root emergence, ovule development, and primary branch formation. Disrupting this IAA-sensing ability induces morphological aberrations with consequences for plant fitness. Therefore, our findings introduce a novel transcription factor-based mechanism of hormone perception in plants. © 2016 Simonini et al.

A model of differential growth guided apical hook formation in plants - Žádníková, Petra; Wabnik, Krzysztof T; Abuzeineh, Anas; Gallemí, Marçal; Van Der Straeten, Dominique; Smith, Richard; Inze, Dirk; Friml, Jirí; Prusinkiewicz, Przemysław; Benková, Eva (Plant Cell)
Differential cell growth enables flexible organ bending in the presence of environmental signals such as light or gravity. A prominent example of the developmental processes based on differential cell growth is the formation of the apical hook that protects the fragile shoot apical meristem when it breaks through the soil during germination. Here, we combined in silico and in vivo approaches to identify a minimal mechanism producing auxin gradient-guided differential growth during the establishment of the apical hook in the model plant Arabidopsis thaliana. Computer simulation models based on experimental data demonstrate that asymmetric expression of the PIN-FORMED auxin efflux carrier at the concave (inner) versus convex (outer) side of the hook suffices to establish an auxin maximum in the epidermis at the concave side of the apical hook. Furthermore, we propose a mechanism that translates this maximum into differential growth, and thus curvature, of the apical hook. Through a combination of experimental and in silico computational approaches, we have identified the individual contributions of differential cell elongation and proliferation to defining the apical hook and reveal the role of auxin-ethylene crosstalk in balancing these two processes. © 2016 American Society of Plant Biologists. All rights reserved.

A microfluidic device for measuring cell migration towards substrate bound and soluble chemokine gradients - Schwarz, Jan; Bierbaum, Veronika; Merrin, Jack; Frank, Tino; Hauschild, Robert; Bollenbach, Mark Tobias; Tay, Savaş; Sixt, Michael K; Mehling, Matthias (Scientific Reports)
Cellular locomotion is a central hallmark of eukaryotic life. It is governed by cell-extrinsic molecular factors, which can either emerge in the soluble phase or as immobilized, often adhesive ligands. To encode for direction, every cue must be present as a spatial or temporal gradient. Here, we developed a microfluidic chamber that allows measurement of cell migration in combined response to surface immobilized and soluble molecular gradients. As a proof of principle we study the response of dendritic cells to their major guidance cues, chemokines. The majority of data on chemokine gradient sensing is based on in vitro studies employing soluble gradients. Despite evidence suggesting that in vivo chemokines are often immobilized to sugar residues, limited information is available how cells respond to immobilized chemokines. We tracked migration of dendritic cells towards immobilized gradients of the chemokine CCL21 and varying superimposed soluble gradients of CCL19. Differential migratory patterns illustrate the potential of our setup to quantitatively study the competitive response to both types of gradients. Beyond chemokines our approach is broadly applicable to alternative systems of chemo- and haptotaxis such as cells migrating along gradients of adhesion receptor ligands vs. any soluble cue.

Tracy-widom distribution for the largest eigenvalue of real sample covariance matrices with general population - Lee, Ji; Schnelli, Kevin (Annals of Applied Probability)
We consider sample covariance matrices of the form Q = ( σ1/2X)(σ1/2X)∗, where the sample X is an M ×N random matrix whose entries are real independent random variables with variance 1/N and whereσ is an M × M positive-definite deterministic matrix. We analyze the asymptotic fluctuations of the largest rescaled eigenvalue of Q when both M and N tend to infinity with N/M →d ϵ (0,∞). For a large class of populations σ in the sub-critical regime, we show that the distribution of the largest rescaled eigenvalue of Q is given by the type-1 Tracy-Widom distribution under the additional assumptions that (1) either the entries of X are i.i.d. Gaussians or (2) that σ is diagonal and that the entries of X have a sub-exponential decay.

Modular parameter identification of biomolecular networks - Lang, Moritz; Stelling, Jörg (SIAM Journal on Scientific Computing)
The increasing complexity of dynamic models in systems and synthetic biology poses computational challenges especially for the identification of model parameters. While modularization of the corresponding optimization problems could help reduce the “curse of dimensionality,” abundant feedback and crosstalk mechanisms prohibit a simple decomposition of most biomolecular networks into subnetworks, or modules. Drawing on ideas from network modularization and multiple-shooting optimization, we present here a modular parameter identification approach that explicitly allows for such interdependencies. Interfaces between our modules are given by the experimentally measured molecular species. This definition allows deriving good (initial) estimates for the inter-module communication directly from the experimental data. Given these estimates, the states and parameter sensitivities of different modules can be integrated independently. To achieve consistency between modules, we iteratively adjust the estimates for inter-module communication while optimizing the parameters. After convergence to an optimal parameter set---but not during earlier iterations---the intermodule communication as well as the individual modules\' state dynamics agree with the dynamics of the nonmodularized network. Our modular parameter identification approach allows for easy parallelization; it can reduce the computational complexity for larger networks and decrease the probability to converge to suboptimal local minima. We demonstrate the algorithm\'s performance in parameter estimation for two biomolecular networks, a synthetic genetic oscillator and a mammalian signaling pathway.

Understanding regulatory networks requires more than computing a multitude of graph statistics: Comment on "Drivers of structural features in gene regulatory networks: From biophysical constraints to biological function" by O. C. Martin et al. - Tkacik, Gasper (Physics of Life Reviews)

Nonequilibrium description of de novo biogenesis and transport through Golgi-like cisternae - Sachdeva, Himani; Barma, Mustansir; Rao, Madan (Scientific Reports)
A central issue in cell biology is the physico-chemical basis of organelle biogenesis in intracellular trafficking pathways, its most impressive manifestation being the biogenesis of Golgi cisternae. At a basic level, such morphologically and chemically distinct compartments should arise from an interplay between the molecular transport and chemical maturation. Here, we formulate analytically tractable, minimalist models, that incorporate this interplay between transport and chemical progression in physical space, and explore the conditions for de novo biogenesis of distinct cisternae. We propose new quantitative measures that can discriminate between the various models of transport in a qualitative manner-this includes measures of the dynamics in steady state and the dynamical response to perturbations of the kind amenable to live-cell imaging.

A closer look at multiple-forking: Leveraging (in)dependence for a tighter bound - Kamath Hosdurg, Chethan; Chatterjee, Sanjit (Algorithmica)
Boldyreva, Palacio and Warinschi introduced a multiple forking game as an extension of general forking. The notion of (multiple) forking is a useful abstraction from the actual simulation of cryptographic scheme to the adversary in a security reduction, and is achieved through the intermediary of a so-called wrapper algorithm. Multiple forking has turned out to be a useful tool in the security argument of several cryptographic protocols. However, a reduction employing multiple forking incurs a significant degradation of (Formula presented.) , where (Formula presented.) denotes the upper bound on the underlying random oracle calls and (Formula presented.) , the number of forkings. In this work we take a closer look at the reasons for the degradation with a tighter security bound in mind. We nail down the exact set of conditions for success in the multiple forking game. A careful analysis of the cryptographic schemes and corresponding security reduction employing multiple forking leads to the formulation of ‘dependence’ and ‘independence’ conditions pertaining to the output of the wrapper in different rounds. Based on the (in)dependence conditions we propose a general framework of multiple forking and a General Multiple Forking Lemma. Leveraging (in)dependence to the full allows us to improve the degradation factor in the multiple forking game by a factor of (Formula presented.). By implication, the cost of a single forking involving two random oracles (augmented forking) matches that involving a single random oracle (elementary forking). Finally, we study the effect of these observations on the concrete security of existing schemes employing multiple forking. We conclude that by careful design of the protocol (and the wrapper in the security reduction) it is possible to harness our observations to the full extent.

Pseudoentropy: Lower-bounds for chain rules and transformations - Pietrzak, Krzysztof Z; Maciej, Skorski
Computational notions of entropy have recently found many applications, including leakage-resilient cryptography, deterministic encryption or memory delegation. The two main types of results which make computational notions so useful are (1) Chain rules, which quantify by how much the computational entropy of a variable decreases if conditioned on some other variable (2) Transformations, which quantify to which extend one type of entropy implies another. Such chain rules and transformations typically lose a significant amount in quality of the entropy, and are the reason why applying these results one gets rather weak quantitative security bounds. In this paper we for the first time prove lower bounds in this context, showing that existing results for transformations are, unfortunately, basically optimal for non-adaptive black-box reductions (and it’s hard to imagine how non black-box reductions or adaptivity could be useful here.) A variable X has k bits of HILL entropy of quality (ϵ,s) if there exists a variable Y with k bits min-entropy which cannot be distinguished from X with advantage ϵ by distinguishing circuits of size s. A weaker notion is Metric entropy, where we switch quantifiers, and only require that for every distinguisher of size s, such a Y exists. We first describe our result concerning transformations. By definition, HILL implies Metric without any loss in quality. Metric entropy often comes up in applications, but must be transformed to HILL for meaningful security guarantees. The best known result states that if a variable X has k bits of Metric entropy of quality (ϵ,s) , then it has k bits of HILL with quality (2ϵ,s⋅ϵ2). We show that this loss of a factor Ω(ϵ−2) in circuit size is necessary. In fact, we show the stronger result that this loss is already necessary when transforming so called deterministic real valued Metric entropy to randomised boolean Metric (both these variants of Metric entropy are implied by HILL without loss in quality). The chain rule for HILL entropy states that if X has k bits of HILL entropy of quality (ϵ,s) , then for any variable Z of length m, X conditioned on Z has k−m bits of HILL entropy with quality (ϵ,s⋅ϵ2/2m). We show that a loss of Ω(2m/ϵ) in circuit size necessary here. Note that this still leaves a gap of ϵ between the known bound and our lower bound.

Neural stem cells to cerebral cortex: Emerging mechanisms regulating progenitor behavior and productivity - Dwyer, Noelle; Chen, Bin; Chou, Shen; Hippenmeyer, Simon; Nguyen, Laurent; Ghashghaei, Troy (Journal of Neuroscience)
This review accompanies a 2016 SFN mini-symposium presenting examples of current studies that address a central question: How do neural stem cells (NSCs) divide in different ways to produce heterogeneous daughter types at the right time and in proper numbers to build a cerebral cortex with the appropriate size and structure? We will focus on four aspects of corticogenesis: cytokinesis events that follow apical mitoses of NSCs; coordinating abscission with delamination from the apical membrane; timing of neurogenesis and its indirect regulation through emergence of intermediate progenitors; and capacity of single NSCs to generate the correct number and laminar fate of cortical neurons. Defects in these mechanisms can cause microcephaly and other brain malformations, and understanding them is critical to designing diagnostic tools and preventive and corrective therapies.

Robust draws in balanced knockout tournaments - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Tkadlec, Josef
Balanced knockout tournaments are ubiquitous in sports competitions and are also used in decisionmaking and elections. The traditional computational question, that asks to compute a draw (optimal draw) that maximizes the winning probability for a distinguished player, has received a lot of attention. Previous works consider the problem where the pairwise winning probabilities are known precisely, while we study how robust is the winning probability with respect to small errors in the pairwise winning probabilities. First, we present several illuminating examples to establish: (a) there exist deterministic tournaments (where the pairwise winning probabilities are 0 or 1) where one optimal draw is much more robust than the other; and (b) in general, there exist tournaments with slightly suboptimal draws that are more robust than all the optimal draws. The above examples motivate the study of the computational problem of robust draws that guarantee a specified winning probability. Second, we present a polynomial-time algorithm for approximating the robustness of a draw for sufficiently small errors in pairwise winning probabilities, and obtain that the stated computational problem is NP-complete. We also show that two natural cases of deterministic tournaments where the optimal draw could be computed in polynomial time also admit polynomial-time algorithms to compute robust optimal draws.

Mating and longevity in ant males - Metzler, Sina; Heinze, Jürgen; Schrempf, Alexandra (Ecology and Evolution)
Across multicellular organisms, the costs of reproduction and self-maintenance result in a life history trade-off between fecundity and longevity. Queens of perennial social Hymenoptera are both highly fertile and long-lived, and thus, this fundamental trade-off is lacking. Whether social insect males similarly evade the fecundity/longevity trade-off remains largely unstudied. Wingless males of the ant genus Cardiocondyla stay in their natal colonies throughout their relatively long lives and mate with multiple female sexuals. Here, we show that Cardiocondyla obscurior males that were allowed to mate with large numbers of female sexuals had a shortened life span compared to males that mated at a low frequency or virgin males. Although frequent mating negatively affects longevity, males clearly benefit from a “live fast, die young strategy” by inseminating as many female sexuals as possible at a cost to their own survival.

Cytokinin response factors integrate auxin and cytokinin pathways for female reproductive organ development - Cucinotta, Mara; Manrique, Silvia; Guazzotti, Andrea; Quadrelli, Nadia; Mendes, Marta; Benková, Eva; Colombo, Lucia (Development)
The developmental programme of the pistil is under the control of both auxin and cytokinin. Crosstalk between these factors converges on regulation of the auxin carrier PIN-FORMED 1 (PIN1). Here, we show that in the triple transcription factor mutant cytokinin response factor 2 (crf2) crf3 crf6 both pistil length and ovule number were reduced. PIN1 expression was also lower in the triple mutant and the phenotypes could not be rescued by exogenous cytokinin application. pin1 complementation studies using genomic PIN1 constructs showed that the pistil phenotypes were only rescued when the PCRE1 domain, to which CRFs bind, was present. Without this domain, pin mutants resemble the crf2 crf3 crf6 triple mutant, indicating the pivotal role of CRFs in auxin-cytokinin crosstalk.

Modular architecture and unique teichoic acid recognition features of choline-binding protein L CbpL contributing to pneumococcal pathogenesis - Gutierrez-Fernandez, Javier; Saleh, Malek; Alcorlo, Martín; Gómez Mejóa, Alejandro; Pantoja Uceda, David; Treviño, Miguel; Vob, Franziska; Abdullah, Mohammed; Galán Bartual, Sergio; Seinen, Jolien; Sánchez Murcia, Pedro; Gago, Federico; et al. (Scientific Reports)
The human pathogen Streptococcus pneumoniae is decorated with a special class of surface-proteins known as choline-binding proteins (CBPs) attached to phosphorylcholine (PCho) moieties from cell-wall teichoic acids. By a combination of X-ray crystallography, NMR, molecular dynamics techniques and in vivo virulence and phagocytosis studies, we provide structural information of choline-binding protein L (CbpL) and demonstrate its impact on pneumococcal pathogenesis and immune evasion. CbpL is a very elongated three-module protein composed of (i) an Excalibur Ca 2+ -binding domain -reported in this work for the very first time-, (ii) an unprecedented anchorage module showing alternate disposition of canonical and non-canonical choline-binding sites that allows vine-like binding of fully-PCho-substituted teichoic acids (with two choline moieties per unit), and (iii) a Ltp-Lipoprotein domain. Our structural and infection assays indicate an important role of the whole multimodular protein allowing both to locate CbpL at specific places on the cell wall and to interact with host components in order to facilitate pneumococcal lung infection and transmigration from nasopharynx to the lungs and blood. CbpL implication in both resistance against killing by phagocytes and pneumococcal pathogenesis further postulate this surface-protein as relevant among the pathogenic arsenal of the pneumococcus.

Asymptotic analysis of noisy fitness maximization, applied to metabolism & growth - De Martino, Daniele; Masoero, Davide (Journal of Statistical Mechanics: Theory and Experiment)
We consider a population dynamics model coupling cell growth to a diffusion in the space of metabolic phenotypes as it can be obtained from realistic constraints-based modelling. In the asymptotic regime of slow diffusion, that coincides with the relevant experimental range, the resulting non-linear Fokker–Planck equation is solved for the steady state in the WKB approximation that maps it into the ground state of a quantum particle in an Airy potential plus a centrifugal term. We retrieve scaling laws for growth rate fluctuations and time response with respect to the distance from the maximum growth rate suggesting that suboptimal populations can have a faster response to perturbations.

Reconstruction of haplotype-blocks selected during experimental evolution. - Franssen, Susan; Barton, Nicholas H; Schlötterer, Christian (Molecular Biology and Evolution)
The genetic analysis of experimentally evolving populations typically relies on short reads from pooled individuals (Pool-Seq). While this method provides reliable allele frequency estimates, the underlying haplotype structure remains poorly characterized. With small population sizes and adaptive variants that start from low frequencies, the interpretation of selection signatures in most Evolve and Resequencing studies remains challenging. To facilitate the characterization of selection targets, we propose a new approach that reconstructs selected haplotypes from replicated time series, using Pool-Seq data. We identify selected haplotypes through the correlated frequencies of alleles carried by them. Computer simulations indicate that selected haplotype-blocks of several Mb can be reconstructed with high confidence and low error rates, even when allele frequencies change only by 20% across three replicates. Applying this method to real data from D. melanogaster populations adapting to a hot environment, we identify a selected haplotype-block of 6.93 Mb. We confirm the presence of this haplotype-block in evolved populations by experimental haplotyping, demonstrating the power and accuracy of our haplotype reconstruction from Pool-Seq data. We propose that the combination of allele frequency estimates with haplotype information will provide the key to understanding the dynamics of adaptive alleles.

Only the combination of mathematics and agent based simulations can leverage the full potential of evolutionary modeling: Comment on “Evolutionary game theory using agent-based methods” by C. Adami, J. Schossau and A. Hintze - Hilbe, Christian; Traulsen, Arne (Physics of Life Reviews)

Formin’ a nuclear protection - Renkawitz, Jörg; Sixt, Michael K (Cell)
In this issue of Cell, Skau et al. show that the formin FMN2 organizes a perinuclear actin cytoskeleton that protects the nucleus and its genomic content of migrating cells squeezing through small spaces.

Immune priming in arthropods: an update focusing on the red flour beetle - Milutinovic, Barbara; Peuß, Robert; Ferro, Kevin; Kurtz, Joachim (Zoology)

Comparative genomic analysis of Haemophilus haemolyticus and nontypeable Haemophilus influenzae and a new testing scheme for their discrimination - Hu, Fang; Rishishwar, Lavanya; Sivadas, Ambily; Mitchell, Gabriel; King, Jordan; Murphy, Timothy; Gilsdorf, Janet; Mayer, Leonard; Wang, Xin (Journal of Clinical Microbiology)
Haemophilus haemolyticus has been recently discovered to have the potential to cause invasive disease. It is closely related to nontypeable Haemophilus influenzae (NT H. influenzae). NT H. influenzae and H. haemolyticus are often misidentified because none of the existing tests targeting the known phenotypes of H. haemolyticus are able to specifically identify H. haemolyticus. Through comparative genomic analysis of H. haemolyticus and NT H. influenzae, we identified genes unique to H. haemolyticus that can be used as targets for the identification of H. haemolyticus. A real-time PCR targeting purT (encoding phosphoribosylglycinamide formyltransferase 2 in the purine synthesis pathway) was developed and evaluated. The lower limit of detection was 40 genomes/PCR; the sensitivity and specificity in detecting H. haemolyticus were 98.9% and 97%, respectively. To improve the discrimination of H. haemolyticus and NT H. influenzae, a testing scheme combining two targets (H. haemolyticus purT and H. influenzae hpd, encoding protein D lipoprotein) was also evaluated and showed 96.7% sensitivity and 98.2% specificity for the identification of H. haemolyticus and 92.8% sensitivity and 100% specificity for the identification of H. influenzae, respectively. The dual-target testing scheme can be used for the diagnosis and surveillance of infection and disease caused by H. haemolyticus and NT H. influenzae.

Surprises in numerical expressions of physical constants - Amir, Ariel; Lemeshko, Mikhail; Tokieda, Tadashi (American Mathematical Monthly)
In science, as in life, "surprises" can be adequately appreciated only in the presence of a null model, what we expect a priori. In physics, theories sometimes express the values of dimensionless physical constants as combinations of mathematical constants like π or e. The inverse problem also arises, whereby the measured value of a physical constant admits a "surprisingly" simple approximation in terms of well-known mathematical constants. Can we estimate the probability for this to be a mere coincidence, rather than an inkling of some theory? We answer the question in the most naive form.

Libration of strongly oriented polar molecules inside a superfluid - Redchenko, Elena; Lemeshko, Mikhail (ChemPhysChem)
We study a polar molecule immersed in a superfluid environment, such as a helium nanodroplet or a Bose–Einstein condensate, in the presence of a strong electrostatic field. We show that coupling of the molecular pendular motion, induced by the field, to the fluctuating bath leads to formation of pendulons—spherical harmonic librators dressed by a field of many-particle excitations. We study the behavior of the pendulon in a broad range of molecule–bath and molecule–field interaction strengths, and reveal that its spectrum features a series of instabilities which are absent in the field-free case of the angulon quasiparticle. Furthermore, we show that an external field allows to fine-tune the positions of these instabilities in the molecular rotational spectrum. This opens the door to detailed experimental studies of redistribution of orbital angular momentum in many-particle systems. © 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim

Purification of ovine respiratory complex i results in a highly active and stable preparation - Letts, James A; Degliesposti, Gianluca; Fiedorczuk, Karol; Skehel, Mark; Sazanov, Leonid A (Journal of Biological Chemistry)
NADH-ubiquinone oxidoreductase (complex I) is the largest (∼1 MDa) and the least characterized complex of the mitochondrial electron transport chain. Because of the ease of sample availability, previous work has focused almost exclusively on bovine complex I. However, only medium resolution structural analyses of this complex have been reported. Working with other mammalian complex I homologues is a potential approach for overcoming these limitations. Due to the inherent difficulty of expressing large membrane protein complexes, screening of complex I homologues is limited to large mammals reared for human consumption. The high sequence identity among these available sources may preclude the benefits of screening. Here, we report the characterization of complex I purified from Ovis aries (ovine) heart mitochondria. All 44 unique subunits of the intact complex were identified by mass spectrometry. We identified differences in the subunit composition of subcomplexes of ovine complex I as compared with bovine, suggesting differential stability of inter-subunit interactions within the complex. Furthermore, the 42-kDa subunit, which is easily lost from the bovine enzyme, remains tightly bound to ovine complex I. Additionally, we developed a novel purification protocol for highly active and stable mitochondrial complex I using the branched-chain detergent lauryl maltose neopentyl glycol. Our data demonstrate that, although closely related, significant differences exist between the biochemical properties of complex I prepared from ovine and bovine mitochondria and that ovine complex I represents a suitable alternative target for further structural studies.

Real time analysis of the apical hook development - Zhu, Qiang; Žádníková, Petra; Smet, Dajo; Van Der Straeten, Dominique; Benková, Eva (Plant Hormones)
Mechanisms for cell protection are essential for survival of multicellular organisms. In plants, the apical hook, which is transiently formed in darkness when the germinating seedling penetrates towards the soil surface, plays such protective role and shields the vitally important shoot apical meristem and cotyledons from damage. The apical hook is formed by bending of the upper hypocotyl soon after germination, and it is maintained in a closed stage while the hypocotyl continues to penetrate through the soil and rapidly opens when exposed to light in proximity of the soil surface. To uncover the complex molecular network orchestrating this spatiotemporally tightly coordinated process, monitoring of the apical hook development in real time is indispensable. Here we describe an imaging platform that enables high-resolution kinetic analysis of this dynamic developmental process. © Springer Science+Business Media New York 2017.

Termination of shoot gravitropic responses by auxin feedback on PIN3 polarity - Rakusová, Hana; Abbas, Mohamad; Han, Huibin; Song, Siyuan; Robert, Hélène; Friml, Jirí (Current Biology)
Plants adjust their growth according to gravity. Gravitropism involves gravity perception, signal transduction, and asymmetric growth response, with organ bending as a consequence [1]. Asymmetric growth results from the asymmetric distribution of the plant-specific signaling molecule auxin [2] that is generated by lateral transport, mediated in the hypocotyl predominantly by the auxin transporter PIN-FORMED3 (PIN3) [3–5]. Gravity stimulation polarizes PIN3 to the bottom sides of endodermal cells, correlating with increased auxin accumulation in adjacent tissues at the lower side of the stimulated organ, where auxin induces cell elongation and, hence, organ bending. A curvature response allows the hypocotyl to resume straight growth at a defined angle [6], implying that at some point auxin symmetry is restored to prevent overbending. Here, we present initial insights into cellular and molecular mechanisms that lead to the termination of the tropic response. We identified an auxin feedback on PIN3 polarization as underlying mechanism that restores symmetry of the PIN3-dependent auxin flow. Thus, two mechanistically distinct PIN3 polarization events redirect auxin fluxes at different time points of the gravity response: first, gravity-mediated redirection of PIN3-mediated auxin flow toward the lower hypocotyl side, where auxin gradually accumulates and promotes growth, and later PIN3 polarization to the opposite cell side, depleting this auxin maximum to end the bending. Accordingly, genetic or pharmacological interference with the late PIN3 polarization prevents termination of the response and leads to hypocotyl overbending. This observation reveals a role of auxin feedback on PIN polarity in the termination of the tropic response. © 2016 Elsevier Ltd

Compliant control for soft robots: Emergent behavior of a tendon driven anthropomorphic arm - Martius, Georg S; Hostettler, Raphael; Knoll, Alois; Der, Ralf
With the accelerated development of robot technologies, optimal control becomes one of the central themes of research. In traditional approaches, the controller, by its internal functionality, finds appropriate actions on the basis of the history of sensor values, guided by the goals, intentions, objectives, learning schemes, and so forth. While very successful with classical robots, these methods run into severe difficulties when applied to soft robots, a new field of robotics with large interest for human-robot interaction. We claim that a novel controller paradigm opens new perspective for this field. This paper applies a recently developed neuro controller with differential extrinsic synaptic plasticity to a muscle-tendon driven arm-shoulder system from the Myorobotics toolkit. In the experiments, we observe a vast variety of self-organized behavior patterns: when left alone, the arm realizes pseudo-random sequences of different poses. By applying physical forces, the system can be entrained into definite motion patterns like wiping a table. Most interestingly, after attaching an object, the controller gets in a functional resonance with the object's internal dynamics, starting to shake spontaneously bottles half-filled with water or sensitively driving an attached pendulum into a circular mode. When attached to the crank of a wheel the neural system independently develops to rotate it. In this way, the robot discovers affordances of objects its body is interacting with.

Acceleration feature points of unsteady shear flows - Kasten, Jens; Reininghaus, Jan; Hotz, Ingrid; Hege, Hans; Noack, Bernd; Daviller, Guillaume; Morzyński, Marek (Archives of Mechanics)
A framework fo r extracting features in 2D transient flows, based on the acceleration field to ensure Galilean invariance is proposed in this paper. The minima of the acceleration magnitude (a superset of acceleration zeros) are extracted and discriminated into vortices and saddle points, based on the spectral properties of the velocity Jacobian. The extraction of topological features is performed with purely combinatorial algorithms from discrete computational topology. The feature points are prioritized with persistence, as a physically meaningful importance measure. These feature points are tracked in time with a robust algorithm for tracking features. Thus, a space-time hierarchy of the minima is built and vortex merging events are detected. We apply the acceleration feature extraction strategy to three two-dimensional shear flows: (1) an incompressible periodic cylinder wake, (2) an incompressible planar mixing layer and (3) a weakly compressible planar jet. The vortex-like acceleration feature points are shown to be well aligned with acceleration zeros, maxima of the vorticity magnitude, minima of the pressure field and minima of λ2.

Efficient T-cell priming and activation requires signaling through prostaglandin E2 (EP) receptors - Sreeramkumar, Vinatha; Hons, Miroslav; Punzón, Carmen; Stein, Jens; Sancho, David; Fresno Forcelledo, Manuel; Cuesta, Natalia (Immunology and Cell Biology)
Understanding the regulation of T-cell responses during inflammation and auto-immunity is fundamental for designing efficient therapeutic strategies against immune diseases. In this regard, prostaglandin E 2 (PGE 2) is mostly considered a myeloid-derived immunosuppressive molecule. We describe for the first time that T cells secrete PGE 2 during T-cell receptor stimulation. In addition, we show that autocrine PGE 2 signaling through EP receptors is essential for optimal CD4 + T-cell activation in vitro and in vivo, and for T helper 1 (Th1) and regulatory T cell differentiation. PGE 2 was found to provide additive co-stimulatory signaling through AKT activation. Intravital multiphoton microscopy showed that triggering EP receptors in T cells is also essential for the stability of T cell-dendritic cell (DC) interactions and Th-cell accumulation in draining lymph nodes (LNs) during inflammation. We further demonstrated that blocking EP receptors in T cells during the initial phase of collagen-induced arthritis in mice resulted in a reduction of clinical arthritis. This could be attributable to defective T-cell activation, accompanied by a decline in activated and interferon-γ-producing CD4 + Th1 cells in draining LNs. In conclusion, we prove that T lymphocytes secret picomolar concentrations of PGE 2, which in turn provide additive co-stimulatory signaling, enabling T cells to attain a favorable activation threshold. PGE 2 signaling in T cells is also required for maintaining long and stable interactions with DCs within LNs. Blockade of EP receptors in vivo impairs T-cell activation and development of T cell-mediated inflammatory responses. This may have implications in various pathophysiological settings.

Culturing synechocystis sp. Strain pcc 6803 with N2 and CO2 in a diel regime reveals multiphase glycogen dynamics with low maintenance costs - Angermayr, Andreas; Van Alphen, Pascal; Hasdemir, Dicle; Kramer, Gertjan; Iqbal, Muzamal; Van Grondelle, Wilmar; Hoefsloot, Huub; Choi, Younghae; Hellingwerf, Klaas (Applied and Environmental Microbiology)
Investigating the physiology of cyanobacteria cultured under a diel light regime is relevant for a better understanding of the resulting growth characteristics and for specific biotechnological applications that are foreseen for these photosynthetic organisms. Here, we present the results of a multiomics study of the model cyanobacterium Synechocystis sp. strain PCC 6803, cultured in a lab-scale photobioreactor in physiological conditions relevant for large-scale culturing. The culture was sparged withN2 andCO2, leading to an anoxic environment during the dark period. Growth followed the availability of light. Metabolite analysis performed with 1Hnuclear magnetic resonance analysis showed that amino acids involved in nitrogen and sulfur assimilation showed elevated levels in the light. Most protein levels, analyzed through mass spectrometry, remained rather stable. However, several high-light-response proteins and stress-response proteins showed distinct changes at the onset of the light period. Microarray-based transcript analysis found common patterns of~56% of the transcriptome following the diel regime. These oscillating transcripts could be grouped coarsely into genes that were upregulated and downregulated in the dark period. The accumulated glycogen was degraded in the anaerobic environment in the dark. A small part was degraded gradually, reflecting basic maintenance requirements of the cells in darkness. Surprisingly, the largest part was degraded rapidly in a short time span at the end of the dark period. This degradation could allow rapid formation of metabolic intermediates at the end of the dark period, preparing the cells for the resumption of growth at the start of the light period.

Bulk universality for deformed wigner matrices - Lee, Jioon; Schnelli, Kevin; Stetler, Ben; Yau, Horngtzer (Annals of Probability)
We consider N×N random matrices of the form H = W + V where W is a real symmetric or complex Hermitian Wigner matrix and V is a random or deterministic, real, diagonal matrix whose entries are independent of W. We assume subexponential decay for the matrix entries of W, and we choose V so that the eigenvalues ofW and V are typically of the same order. For a large class of diagonal matrices V , we show that the local statistics in the bulk of the spectrum are universal in the limit of large N.

Fuselage boundary layer ingestion propulsion applied to a thin haul commuter aircraft for optimal efficiency - Mikić, Gregor; Stoll, Alex; Bevirt, Joe; Grah, Rok; Moore, Mark
Theoretical and numerical aspects of aerodynamic efficiency of propulsion systems coupled to the boundary layer of a fuselage are studied. We discuss the effects of local flow fields, which are affected both by conservative flow acceleration as well as total pressure losses, on the efficiency of boundary layer immersed propulsion devices. We introduce the concept of a boundary layer retardation turbine that helps reduce skin friction over the fuselage. We numerically investigate efficiency gains offered by boundary layer and wake interacting devices. We discuss the results in terms of a total energy consumption framework and show that efficiency gains of any device depend on all the other elements of the propulsion system.

Strong morphological defects in conditional Arabidopsis abp1 knock-down mutants generated in absence of functional ABP1 protein - Michalko, Jaroslav; Glanc, Matous; Perrot Rechenmann, Catherine; Friml, Jirí (F1000 Research)
The Auxin Binding Protein 1 (ABP1) is one of the most studied proteins in plants. Since decades ago, it has been the prime receptor candidate for the plant hormone auxin with a plethora of described functions in auxin signaling and development. The developmental importance of ABP1 has recently been questioned by identification of Arabidopsis thaliana abp1 knock-out alleles that show no obvious phenotypes under normal growth conditions. In this study, we examined the contradiction between the normal growth and development of the abp1 knock-outs and the strong morphological defects observed in three different ethanol-inducible abp1 knock-down mutants ( abp1-AS, SS12K, SS12S). By analyzing segregating populations of abp1 knock-out vs. abp1 knock-down crosses we show that the strong morphological defects that were believed to be the result of conditional down-regulation of ABP1 can be reproduced also in the absence of the functional ABP1 protein. This data suggests that the phenotypes in abp1 knock-down lines are due to the off-target effects and asks for further reflections on the biological function of ABP1 or alternative explanations for the missing phenotypic defects in the abp1 loss-of-function alleles.

Optimal packings of congruent circles on a square flat torus - Musin, Oleg; Nikitenko, Anton (Discrete & Computational Geometry)
We consider packings of congruent circles on a square flat torus, i.e., periodic (w.r.t. a square lattice) planar circle packings, with the maximal circle radius. This problem is interesting due to a practical reason—the problem of “super resolution of images.” We have found optimal arrangements for N=6, 7 and 8 circles. Surprisingly, for the case N=7 there are three different optimal arrangements. Our proof is based on a computer enumeration of toroidal irreducible contact graphs.

Localization for transversally periodic random potentials on binary trees - Froese, Richard; Lee, Darrick; Sadel, Christian; Spitzer, Wolfgang; Stolz, Günter (Journal of Spectral Theory)
We consider a random Schrödinger operator on the binary tree with a random potential which is the sum of a random radially symmetric potential, Qr, and a random transversally periodic potential, κQt, with coupling constant κ. Using a new one-dimensional dynamical systems approach combined with Jensen's inequality in hyperbolic space (our key estimate) we obtain a fractional moment estimate proving localization for small and large κ. Together with a previous result we therefore obtain a model with two Anderson transitions, from localization to delocalization and back to localization, when increasing κ. As a by-product we also have a partially new proof of one-dimensional Anderson localization at any disorder.

The dynamics of resource allocation and costs of reproduction in a sexually dimorphic, wind-pollinated dioecious plant - Teitel, Zachary; Pickup, Melinda; Field, David; Barrett, Spencer (Plant Biology)
Sexual dimorphism in resource allocation is expected to change during the life cycle of dioecious plants because of temporal differences between the sexes in reproductive investment. Given the potential for sex-specific differences in reproductive costs, resource availability may contribute to variation in reproductive allocation in females and males. Here, we used Rumex hastatulus, a dioecious, wind-pollinated annual plant, to investigate whether sexual dimorphism varies with life-history stage and nutrient availability, and determine whether allocation patterns differ depending on reproductive commitment. To examine if the costs of reproduction varied between the sexes, reproduction was either allowed or prevented through bud removal, and biomass allocation was measured at maturity. In a second experiment to assess variation in sexual dimorphism across the life cycle, and whether this varied with resource availability, plants were grown in high and low nutrients and allocation to roots, aboveground vegetative growth and reproduction were measured at three developmental stages. Males prevented from reproducing compensated with increased above- and belowground allocation to a much larger degree than females, suggesting that male reproductive costs reduce vegetative growth. The proportional allocation to roots, reproductive structures and aboveground vegetative growth varied between the sexes and among life-cycle stages, but not with nutrient treatment. Females allocated proportionally more resources to roots than males at peak flowering, but this pattern was reversed at reproductive maturity under low-nutrient conditions. Our study illustrates the importance of temporal dynamics in sex-specific resource allocation and provides support for high male reproductive costs in wind-pollinated plants.

Atomic structure of the entire mammalian mitochondrial complex i - Fiedorczuk, Karol; Letts, James A; Degliesposti, Gianluca; Kaszuba, Karol; Skehel, Mark; Sazanov, Leonid A (Nature)
Mitochondrial complex I (also known as NADH:ubiquinone oxidoreductase) contributes to cellular energy production by transferring electrons from NADH to ubiquinone coupled to proton translocation across the membrane. It is the largest protein assembly of the respiratory chain with a total mass of 970 kilodaltons. Here we present a nearly complete atomic structure of ovine (Ovis aries) mitochondrial complex I at 3.9 Å resolution, solved by cryo-electron microscopy with cross-linking and mass-spectrometry mapping experiments. All 14 conserved core subunits and 31 mitochondria-specific supernumerary subunits are resolved within the L-shaped molecule. The hydrophilic matrix arm comprises flavin mononucleotide and 8 iron-sulfur clusters involved in electron transfer, and the membrane arm contains 78 transmembrane helices, mostly contributed by antiporter-like subunits involved in proton translocation. Supernumerary subunits form an interlinked, stabilizing shell around the conserved core. Tightly bound lipids (including cardiolipins) further stabilize interactions between the hydrophobic subunits. Subunits with possible regulatory roles contain additional cofactors, NADPH and two phosphopantetheine molecules, which are shown to be involved in inter-subunit interactions. We observe two different conformations of the complex, which may be related to the conformationally driven coupling mechanism and to the active-deactive transition of the enzyme. Our structure provides insight into the mechanism, assembly, maturation and dysfunction of mitochondrial complex I, and allows detailed molecular analysis of disease-causing mutations.

Discrete abstraction of multiaffine systems - Kong, Hui; Bartocci, Ezio; Bogomolov, Sergiy; Grosu, Radu; Henzinger, Thomas A; Jiang, Yu; Schilling, Christian
Many biological systems can be modeled as multiaffine hybrid systems. Due to the nonlinearity of multiaffine systems, it is difficult to verify their properties of interest directly. A common strategy to tackle this problem is to construct and analyze a discrete overapproximation of the original system. However, the conservativeness of a discrete abstraction significantly determines the level of confidence we can have in the properties of the original system. In this paper, in order to reduce the conservativeness of a discrete abstraction, we propose a new method based on a sufficient and necessary decision condition for computing discrete transitions between states in the abstract system. We assume the state space partition of a multiaffine system to be based on a set of multivariate polynomials. Hence, a rectangular partition defined in terms of polynomials of the form (xi − c) is just a simple case of multivariate polynomial partition, and the new decision condition applies naturally. We analyze and demonstrate the improvement of our method over the existing methods using some examples.

On the complexity of scrypt and proofs of space in the parallel random oracle model - Alwen, Joel F; Chen, Binyi; Kamath Hosdurg, Chethan; Kolmogorov, Vladimir; Pietrzak, Krzysztof Z; Tessaro, Stefano
We study the time-and memory-complexities of the problem of computing labels of (multiple) randomly selected challenge-nodes in a directed acyclic graph. The w-bit label of a node is the hash of the labels of its parents, and the hash function is modeled as a random oracle. Specific instances of this problem underlie both proofs of space [Dziembowski et al. CRYPTO’15] as well as popular memory-hard functions like scrypt. As our main tool, we introduce the new notion of a probabilistic parallel entangled pebbling game, a new type of combinatorial pebbling game on a graph, which is closely related to the labeling game on the same graph. As a first application of our framework, we prove that for scrypt, when the underlying hash function is invoked n times, the cumulative memory complexity (CMC) (a notion recently introduced by Alwen and Serbinenko (STOC’15) to capture amortized memory-hardness for parallel adversaries) is at least Ω(w · (n/ log(n))2). This bound holds for adversaries that can store many natural functions of the labels (e.g., linear combinations), but still not arbitrary functions thereof. We then introduce and study a combinatorial quantity, and show how a sufficiently small upper bound on it (which we conjecture) extends our CMC bound for scrypt to hold against arbitrary adversaries. We also show that such an upper bound solves the main open problem for proofs-of-space protocols: namely, establishing that the time complexity of computing the label of a random node in a graph on n nodes (given an initial kw-bit state) reduces tightly to the time complexity for black pebbling on the same graph (given an initial k-node pebbling).

The architecture of respiratory supercomplexes - Letts, James A; Fiedorczuk, Karol; Sazanov, Leonid A (Nature)
Mitochondrial electron transport chain complexes are organized into supercomplexes responsible for carrying out cellular respiration. Here we present three architectures of mammalian (ovine) supercomplexes determined by cryo-electron microscopy. We identify two distinct arrangements of supercomplex CICIII 2 CIV (the respirasome) - a major 'tight' form and a minor 'loose' form (resolved at the resolution of 5.8 Å and 6.7 Å, respectively), which may represent different stages in supercomplex assembly or disassembly. We have also determined an architecture of supercomplex CICIII 2 at 7.8 Å resolution. All observed density can be attributed to the known 80 subunits of the individual complexes, including 132 transmembrane helices. The individual complexes form tight interactions that vary between the architectures, with complex IV subunit COX7a switching contact from complex III to complex I. The arrangement of active sites within the supercomplex may help control reactive oxygen species production. To our knowledge, these are the first complete architectures of the dominant, physiologically relevant state of the electron transport chain.

Standard security does imply security against selective opening for markov distributions - Fuchsbauer, Georg; Heuer, Felix; Kiltz, Eike; Pietrzak, Krzysztof Z
About three decades ago it was realized that implementing private channels between parties which can be adaptively corrupted requires an encryption scheme that is secure against selective opening attacks. Whether standard (IND-CPA) security implies security against selective opening attacks has been a major open question since. The only known reduction from selective opening to IND-CPA security loses an exponential factor. A polynomial reduction is only known for the very special case where the distribution considered in the selective opening security experiment is a product distribution, i.e., the messages are sampled independently from each other. In this paper we give a reduction whose loss is quantified via the dependence graph (where message dependencies correspond to edges) of the underlying message distribution. In particular, for some concrete distributions including Markov distributions, our reduction is polynomial.

Endosomal interactions during root hair growth - Von Wangenheim, Daniel; Rosero, Amparo; Komis, George; Šamajová, Olga; Ovečka, Miroslav; Voigt, Boris; Šamaj, Jozef (Frontiers in Plant Science)
The dynamic localization of endosomal compartments labeled with targeted fluorescent protein tags is routinely followed by time lapse fluorescence microscopy approaches and single particle tracking algorithms. In this way trajectories of individual endosomes can be mapped and linked to physiological processes as cell growth. However, other aspects of dynamic behavior including endosomal interactions are difficult to follow in this manner. Therefore, we characterized the localization and dynamic properties of early and late endosomes throughout the entire course of root hair formation by means of spinning disc time lapse imaging and post-acquisition automated multitracking and quantitative analysis. Our results show differential motile behavior of early and late endosomes and interactions of late endosomes that may be specified to particular root hair domains. Detailed data analysis revealed a particular transient interaction between late endosomes—termed herein as dancing-endosomes—which is not concluding to vesicular fusion. Endosomes preferentially located in the root hair tip interacted as dancing-endosomes and traveled short distances during this interaction. Finally, sizes of early and late endosomes were addressed by means of super-resolution structured illumination microscopy (SIM) to corroborate measurements on the spinning disc. This is a first study providing quantitative microscopic data on dynamic spatio-temporal interactions of endosomes during root hair tip growth.

Computation of cubical Steenrod squares - Krcál, Marek; Pilarczyk, Pawel
Bitmap images of arbitrary dimension may be formally perceived as unions of m-dimensional boxes aligned with respect to a rectangular grid in ℝm. Cohomology and homology groups are well known topological invariants of such sets. Cohomological operations, such as the cup product, provide higher-order algebraic topological invariants, especially important for digital images of dimension higher than 3. If such an operation is determined at the level of simplicial chains [see e.g. González-Díaz, Real, Homology, Homotopy Appl, 2003, 83-93], then it is effectively computable. However, decomposing a cubical complex into a simplicial one deleteriously affects the efficiency of such an approach. In order to avoid this overhead, a direct cubical approach was applied in [Pilarczyk, Real, Adv. Comput. Math., 2015, 253-275] for the cup product in cohomology, and implemented in the ChainCon software package [http://www.pawelpilarczyk.com/chaincon/]. We establish a formula for the Steenrod square operations [see Steenrod, Annals of Mathematics. Second Series, 1947, 290-320] directly at the level of cubical chains, and we prove the correctness of this formula. An implementation of this formula is programmed in C++ within the ChainCon software framework. We provide a few examples and discuss the effectiveness of this approach. One specific application follows from the fact that Steenrod squares yield tests for the topological extension problem: Can a given map A → Sd to a sphere Sd be extended to a given super-complex X of A? In particular, the ROB-SAT problem, which is to decide for a given function f: X → ℝm and a value r > 0 whether every g: X → ℝm with ∥g - f ∥∞ ≤ r has a root, reduces to the extension problem.

Long non-coding RNAs display higher natural expression variation than protein-coding genes in healthy humans - Kornienko, Aleksandra; Dotter, Christoph; Guenzl, Philipp; Gisslinger, Heinz; Gisslinger, Bettina; Cleary, Ciara; Kralovics, Robert; Pauler, Florian; Barlow, Denise (Genome Biology)
Background: Long non-coding RNAs (lncRNAs) are increasingly implicated as gene regulators and may ultimately be more numerous than protein-coding genes in the human genome. Despite large numbers of reported lncRNAs, reference annotations are likely incomplete due to their lower and tighter tissue-specific expression compared to mRNAs. An unexplored factor potentially confounding lncRNA identification is inter-individual expression variability. Here, we characterize lncRNA natural expression variability in human primary granulocytes. Results: We annotate granulocyte lncRNAs and mRNAs in RNA-seq data from 10 healthy individuals, identifying multiple lncRNAs absent from reference annotations, and use this to investigate three known features (higher tissue-specificity, lower expression, and reduced splicing efficiency) of lncRNAs relative to mRNAs. Expression variability was examined in seven individuals sampled three times at 1- or more than 1-month intervals. We show that lncRNAs display significantly more inter-individual expression variability compared to mRNAs. We confirm this finding in two independent human datasets by analyzing multiple tissues from the GTEx project and lymphoblastoid cell lines from the GEUVADIS project. Using the latter dataset we also show that including more human donors into the transcriptome annotation pipeline allows identification of an increasing number of lncRNAs, but minimally affects mRNA gene number. Conclusions: A comprehensive annotation of lncRNAs is known to require an approach that is sensitive to low and tight tissue-specific expression. Here we show that increased inter-individual expression variability is an additional general lncRNA feature to consider when creating a comprehensive annotation of human lncRNAs or proposing their use as prognostic or disease markers.

Cortical flow-driven shapes of nonadherent cells - Callan Jones, Andrew; Ruprecht, Verena; Wieser, Stefan; Heisenberg, Carl-Philipp J; Voituriez, Raphaël (Physical Review Letters)
Nonadherent polarized cells have been observed to have a pearlike, elongated shape. Using a minimal model that describes the cell cortex as a thin layer of contractile active gel, we show that the anisotropy of active stresses, controlled by cortical viscosity and filament ordering, can account for this morphology. The predicted shapes can be determined from the flow pattern only; they prove to be independent of the mechanism at the origin of the cortical flow, and are only weakly sensitive to the cytoplasmic rheology. In the case of actin flows resulting from a contractile instability, we propose a phase diagram of three-dimensional cell shapes that encompasses nonpolarized spherical, elongated, as well as oblate shapes, all of which have been observed in experiment.

Extending the dynamic range of transcription factor action by translational regulation - Sokolowski, Thomas R; Walczak, Aleksandra; Bialek, William; Tkacik, Gasper (Physical Review E Statistical Nonlinear and Soft Matter Physics)
A crucial step in the regulation of gene expression is binding of transcription factor (TF) proteins to regulatory sites along the DNA. But transcription factors act at nanomolar concentrations, and noise due to random arrival of these molecules at their binding sites can severely limit the precision of regulation. Recent work on the optimization of information flow through regulatory networks indicates that the lower end of the dynamic range of concentrations is simply inaccessible, overwhelmed by the impact of this noise. Motivated by the behavior of homeodomain proteins, such as the maternal morphogen Bicoid in the fruit fly embryo, we suggest a scheme in which transcription factors also act as indirect translational regulators, binding to the mRNA of other regulatory proteins. Intuitively, each mRNA molecule acts as an independent sensor of the input concentration, and averaging over these multiple sensors reduces the noise. We analyze information flow through this scheme and identify conditions under which it outperforms direct transcriptional regulation. Our results suggest that the dual role of homeodomain proteins is not just a historical accident, but a solution to a crucial physics problem in the regulation of gene expression.

The role of recombination in evolutionary rescue - Uecker, Hildegard; Hermisson, Joachim (Genetics)
How likely is it that a population escapes extinction through adaptive evolution? The answer to this question is of great relevance in conservation biology, where we aim at species’ rescue and the maintenance of biodiversity, and in agriculture and medicine, where we seek to hamper the emergence of pesticide or drug resistance. By reshuffling the genome, recombination has two antagonistic effects on the probability of evolutionary rescue: It generates and it breaks up favorable gene combinations. Which of the two effects prevails depends on the fitness effects of mutations and on the impact of stochasticity on the allele frequencies. In this article, we analyze a mathematical model for rescue after a sudden environmental change when adaptation is contingent on mutations at two loci. The analysis reveals a complex nonlinear dependence of population survival on recombination. We moreover find that, counterintuitively, a fast eradication of the wild type can promote rescue in the presence of recombination. The model also shows that two-step rescue is not unlikely to happen and can even be more likely than single-step rescue (where adaptation relies on a single mutation), depending on the circumstances.

ROTUNDA3 function in plant development by phosphatase 2A-mediated regulation of auxin transporter recycling - Karampelias, Michael; Neyt, Pia; De Groeve, Steven; Aesaert, Stijn; Coussens, Griet; Rolčík, Jakub; Bruno, Leonardo; De Winne, Nancy; Van Minnebruggen, Annemie; Van Montagu, Marc; Ponce, Maria; Micol, José; et al. (PNAS)
The shaping of organs in plants depends on the intercellular flow of the phytohormone auxin, of which the directional signaling is determined by the polar subcellular localization of PIN-FORMED (PIN) auxin transport proteins. Phosphorylation dynamics of PIN proteins are affected by the protein phosphatase 2A (PP2A) and the PINOID kinase, which act antagonistically to mediate their apical-basal polar delivery. Here, we identified the ROTUNDA3 (RON3) protein as a regulator of the PP2A phosphatase activity in Arabidopsis thaliana. The RON3 gene was map-based cloned starting from the ron3-1 leaf mutant and found to be a unique, plant-specific gene coding for a protein with high and dispersed proline content. The ron3-1 and ron3-2 mutant phenotypes [i.e., reduced apical dominance, primary root length, lateral root emergence, and growth; increased ectopic stages II, IV, and V lateral root primordia; decreased auxin maxima in indole-3-acetic acid (IAA)-treated root apical meristems; hypergravitropic root growth and response; increased IAA levels in shoot apices; and reduced auxin accumulation in root meristems] support a role for RON3 in auxin biology. The affinity-purified PP2A complex with RON3 as bait suggested that RON3 might act in PIN transporter trafficking. Indeed, pharmacological interference with vesicle trafficking processes revealed that single ron3-2 and double ron3-2 rcn1 mutants have altered PIN polarity and endocytosis in specific cells. Our data indicate that RON3 contributes to auxin-mediated development by playing a role in PIN recycling and polarity establishment through regulation of the PP2A complex activity.

Imaging of electric and magnetic fields near plasmonic nanowires - Kabakova, Irina; De Hoogh, Anouk; Van Der Wel, Ruben; Wulf, Matthias; Le Feber, Boris; Kuipers, Laurens (Scientific Reports)
Near-field imaging is a powerful tool to investigate the complex structure of light at the nanoscale. Recent advances in near-field imaging have indicated the possibility for the complete reconstruction of both electric and magnetic components of the evanescent field. Here we study the electro-magnetic field structure of surface plasmon polariton waves propagating along subwavelength gold nanowires by performing phase- and polarization-resolved near-field microscopy in collection mode. By applying the optical reciprocity theorem, we describe the signal collected by the probe as an overlap integral of the nanowire's evanescent field and the probe's response function. As a result, we find that the probe's sensitivity to the magnetic field is approximately equal to its sensitivity to the electric field. Through rigorous modeling of the nanowire mode as well as the aperture probe response function, we obtain a good agreement between experimentally measured signals and a numerical model. Our findings provide a better understanding of aperture-based near-field imaging of the nanoscopic plasmonic and photonic structures and are helpful for the interpretation of future near-field experiments.

Game-theoretic models identify useful principles for peer collaboration in online learning platforms - Pandey, Vineet; Chatterjee, Krishnendu (Proceedings of the ACM Conference on Computer Supported Cooperative Work)
To facilitate collaboration in massive online classrooms, instructors must make many decisions. For instance, the following parameters need to be decided when designing a peer-feedback system where students review each others' essays: the number of students each student must provide feedback to, an algorithm to map feedback providers to receivers, constraints that ensure students do not become free-riders (receiving feedback but not providing it), the best times to receive feedback to improve learning etc. While instructors can answer these questions by running experiments or invoking past experience, game-theoretic models with data from online learning platforms can identify better initial designs for further improvements. As an example, we explore the design space of a peer feedback system by modeling it using game theory. Our simulations show that incentivizing students to provide feedback requires the value obtained from receiving a feedback to exceed the cost of providing it by a large factor (greater than 7). Furthermore, hiding feedback from low-effort students incentivizes them to provide more feedback.

Chimera proteins with affinity for membranes and microtubule tips polarize in the membrane of fission yeast cells - Recouvreux, Pierre; Sokolowski, Thomas R; Grammoustianou, Aristea; Tenwolde, Pieter; Dogterom, Marileen (PNAS)
Cell polarity refers to a functional spatial organization of proteins that is crucial for the control of essential cellular processes such as growth and division. To establish polarity, cells rely on elaborate regulation networks that control the distribution of proteins at the cell membrane. In fission yeast cells, a microtubule-dependent network has been identified that polarizes the distribution of signaling proteins that restricts growth to cell ends and targets the cytokinetic machinery to the middle of the cell. Although many molecular components have been shown to play a role in this network, it remains unknown which molecular functionalities are minimally required to establish a polarized protein distribution in this system. Here we show that a membrane-binding protein fragment, which distributes homogeneously in wild-type fission yeast cells, can be made to concentrate at cell ends by attaching it to a cytoplasmic microtubule end-binding protein. This concentration results in a polarized pattern of chimera proteins with a spatial extension that is very reminiscent of natural polarity patterns in fission yeast. However, chimera levels fluctuate in response to microtubule dynamics, and disruption of microtubules leads to disappearance of the pattern. Numerical simulations confirm that the combined functionality of membrane anchoring and microtubule tip affinity is in principle sufficient to create polarized patterns. Our chimera protein may thus represent a simple molecular functionality that is able to polarize the membrane, onto which additional layers of molecular complexity may be built to provide the temporal robustness that is typical of natural polarity patterns.

Information processing in living systems - Tkacik, Gasper; Bialek, William (Annual Review of Condensed Matter Physics)
Life depends as much on the flow of information as on the flow of energy. Here we review the many efforts to make this intuition precise. Starting with the building blocks of information theory, we explore examples where it has been possible to measure, directly, the flow of information in biological networks, or more generally where information-theoretic ideas have been used to guide the analysis of experiments. Systems of interest range from single molecules (the sequence diversity in families of proteins) to groups of organisms (the distribution of velocities in flocks of birds), and all scales in between. Many of these analyses are motivated by the idea that biological systems may have evolved to optimize the gathering and representation of information, and we review the experimental evidence for this optimization, again across a wide range of scales.

Determining physical properties of the cell cortex - Saha, Arnab; Nishikawa, Masatoshi; Behrndt, Martin; Heisenberg, Carl-Philipp J; Julicher, Frank; Grill, Stephan (Biophysical Journal)
Actin and myosin assemble into a thin layer of a highly dynamic network underneath the membrane of eukaryotic cells. This network generates the forces that drive cell- and tissue-scale morphogenetic processes. The effective material properties of this active network determine large-scale deformations and other morphogenetic events. For example, the characteristic time of stress relaxation (the Maxwell time τM) in the actomyosin sets the timescale of large-scale deformation of the cortex. Similarly, the characteristic length of stress propagation (the hydrodynamic length λ) sets the length scale of slow deformations, and a large hydrodynamic length is a prerequisite for long-ranged cortical flows. Here we introduce a method to determine physical parameters of the actomyosin cortical layer in vivo directly from laser ablation experiments. For this we investigate the cortical response to laser ablation in the one-cell-stage Caenorhabditis elegans embryo and in the gastrulating zebrafish embryo. These responses can be interpreted using a coarse-grained physical description of the cortex in terms of a two-dimensional thin film of an active viscoelastic gel. To determine the Maxwell time τM, the hydrodynamic length λ, the ratio of active stress ζΔμ, and per-area friction γ, we evaluated the response to laser ablation in two different ways: by quantifying flow and density fields as a function of space and time, and by determining the time evolution of the shape of the ablated region. Importantly, both methods provide best-fit physical parameters that are in close agreement with each other and that are similar to previous estimates in the two systems. Our method provides an accurate and robust means for measuring physical parameters of the actomyosin cortical layer. It can be useful for investigations of actomyosin mechanics at the cellular-scale, but also for providing insights into the active mechanics processes that govern tissue-scale morphogenesis.

TWISTED DWARF1 mediates the action of auxin transport inhibitors on actin cytoskeleton dynamics - Zhu, Jinsheng; Bailly, Aurélien; Zwiewka, Marta; Sovero, Valpuri; Di Donato, Martin; Ge, Pei; Oehri, Jacqueline; Aryal, Bibek; Hao, Pengchao; Linnert, Miriam; Burgardt, Noelia; Lücke, Christian; et al. (Plant Cell)
Plant growth and architecture is regulated by the polar distribution of the hormone auxin. Polarity and flexibility of this process is provided by constant cycling of auxin transporter vesicles along actin filaments, coordinated by a positive auxinactin feedback loop. Both polar auxin transport and vesicle cycling are inhibited by synthetic auxin transport inhibitors, such as 1-Nnaphthylphthalamic acid (NPA), counteracting the effect of auxin; however, underlying targets and mechanisms are unclear. Using NMR, we map the NPA binding surface on the Arabidopsis thaliana ABCB chaperone TWISTED DWARF1 (TWD1).We identify ACTIN7 as a relevant, although likely indirect, TWD1 interactor, and show TWD1-dependent regulation of actin filament organization and dynamics and that TWD1 is required for NPA-mediated actin cytoskeleton remodeling. The TWD1-ACTIN7 axis controls plasma membrane presence of efflux transporters, and as a consequence act7 and twd1 share developmental and physiological phenotypes indicative of defects in auxin transport. These can be phenocopied by NPA treatment or by chemical actin (de)stabilization. We provide evidence that TWD1 determines downstreamlocations of auxin efflux transporters by adjusting actin filament debundling and dynamizing processes and mediating NPA action on the latter. This function appears to be evolutionary conserved since TWD1 expression in budding yeast alters actin polarization and cell polarity and provides NPA sensitivity.

Inducing a map on homology from a correspondence - Harker, Shaun; Kokubu, Hiroshi; Mischaikow, Konstantin; Pilarczyk, Pawel (Proceedings of the American Mathematical Society)
We study the homomorphism induced in homology by a closed correspondence between topological spaces, using projections from the graph of the correspondence to its domain and codomain. We provide assumptions under which the homomorphism induced by an outer approximation of a continuous map coincides with the homomorphism induced in homology by the map. In contrast to more classical results we do not require that the projection to the domain have acyclic preimages. Moreover, we show that it is possible to retrieve correct homological information from a correspondence even if some data is missing or perturbed. Finally, we describe an application to combinatorial maps that are either outer approximations of continuous maps or reconstructions of such maps from a finite set of data points.

Uniform expansivity outside a critical neighborhood in the quadratic family - Golmakani, Ali; Luzzatto, Stefano; Pilarczyk, Pawel (Experimental Mathematics)
We use rigorous numerical techniques to compute a lower bound for the exponent of expansivity outside a neighborhood of the critical point for thousands of intervals of parameter values in the quadratic family. We first compute a radius of the critical neighborhood outside which the map is uniformly expanding. This radius is taken as small as possible, yet large enough for our numerical procedure to succeed in proving that the expansivity exponent outside this neighborhood is positive. Then, for each of the intervals, we compute a lower bound for this expansivity exponent, valid for all the parameters in that interval. We illustrate and study the distribution of the radii and the expansivity exponents. The results of our computations are mathematically rigorous. The source code of the software and the results of the computations are made publicly available at http://www.pawelpilarczyk.com/quadratic/.

Down syndrome cell adhesion molecule 1: Testing for a role in insect immunity, behaviour and reproduction - Peuß, Robert; Wensing, Kristina; Woestmann, Luisa; Eggert, Hendrik; Milutinovic, Barbara; Sroka, Marlene; Scharsack, Jörn; Kurtz, Joachim; Armitage, Sophie (Royal Society Open Science)
Down syndrome cell adhesion molecule 1 (Dscam1) has widereaching and vital neuronal functions although the role it plays in insect and crustacean immunity is less well understood. In this study, we combine different approaches to understand the roles that Dscam1 plays in fitness-related contexts in two model insect species. Contrary to our expectations, we found no short-term modulation of Dscam1 gene expression after haemocoelic or oral bacterial exposure in Tribolium castaneum, or after haemocoelic bacterial exposure in Drosophila melanogaster. Furthermore, RNAi-mediated Dscam1 knockdown and subsequent bacterial exposure did not reduce T. castaneum survival. However, Dscam1 knockdown in larvae resulted in adult locomotion defects, as well as dramatically reduced fecundity in males and females. We suggest that Dscam1 does not always play a straightforward role in immunity, but strongly influences behaviour and fecundity. This study takes a step towards understanding more about the role of this intriguing gene from different phenotypic perspectives.

From stateflow simulation to verified implementation: A verification approach and a real-time train controller design - Jiang, Yu; Yang, Yixiao; Liu, Han; Kong, Hui; Gu, Ming; Sun, Jiaguang; Sha, Lui
Simulink is widely used for model driven development (MDD) of industrial software systems. Typically, the Simulink based development is initiated from Stateflow modeling, followed by simulation, validation and code generation mapped to physical execution platforms. However, recent industrial trends have raised the demands of rigorous verification on safety-critical applications, which is unfortunately challenging for Simulink. In this paper, we present an approach to bridge the Stateflow based model driven development and a well- defined rigorous verification. First, we develop a self- contained toolkit to translate Stateflow model into timed automata, where major advanced modeling features in Stateflow are supported. Taking advantage of the strong verification capability of Uppaal, we can not only find bugs in Stateflow models which are missed by Simulink Design Verifier, but also check more important temporal properties. Next, we customize a runtime verifier for the generated nonintrusive VHDL and C code of Stateflow model for monitoring. The major strength of the customization is the flexibility to collect and analyze runtime properties with a pure software monitor, which opens more opportunities for engineers to achieve high reliability of the target system compared with the traditional act that only relies on Simulink Polyspace. We incorporate these two parts into original Stateflow based MDD seamlessly. In this way, safety-critical properties are both verified at the model level, and at the consistent system implementation level with physical execution environment in consideration. We apply our approach on a train controller design, and the verified implementation is tested and deployed on a real hardware platform.

A central limit theorem for products of random matrices and GOE statistics for the Anderson model on long boxes - Sadel, Christian; Virág, Bálint (Communications in Mathematical Physics)
We consider products of random matrices that are small, independent identically distributed perturbations of a fixed matrix (Formula presented.). Focusing on the eigenvalues of (Formula presented.) of a particular size we obtain a limit to a SDE in a critical scaling. Previous results required (Formula presented.) to be a (conjugated) unitary matrix so it could not have eigenvalues of different modulus. From the result we can also obtain a limit SDE for the Markov process given by the action of the random products on the flag manifold. Applying the result to random Schrödinger operators we can improve some results by Valko and Virag showing GOE statistics for the rescaled eigenvalue process of a sequence of Anderson models on long boxes. In particular, we solve a problem posed in their work.

DRACULA2 is a dynamic nucleoporin with a role in regulating the shade avoidance syndrome in Arabidopsis - Gallemi Rovira, Marcal; Galstyan, Anahit; Paulišić, Sandi; Then, Christiane; Ferrández Ayela, Almudena; Lorenzo Orts, Laura; Roig Villanova, Irma; Wang, Xuewen; Micol, José; Ponce, Maria; Devlin, Paul; Martínez García, Jaime (Development)
When plants grow in close proximity basic resources such as light can become limiting. Under such conditions plants respond to anticipate and/or adapt to the light shortage, a process known as the shade avoidance syndrome (SAS). Following genetic screening using a shade-responsive luciferase reporter line (PHYB:LUC), we identified DRACULA2 (DRA2), which encodes an Arabidopsis homolog of mammalian nucleoporin 98, a component of the nuclear pore complex (NPC). DRA2, together with other nucleoporins, participates positively in the control of the hypocotyl elongation response to plant proximity, a role that can be considered dependent on the nucleocytoplasmic transport of macromolecules (i.e. is transport dependent). In addition, our results reveal a specific role for DRA2 in controlling shade-induced gene expression. We suggest that this novel regulatory role of DRA2 is transport independent and that it might rely on its dynamic localization within and outside of the NPC. These results provide mechanistic insights in to how SAS responses are rapidly established by light conditions. They also indicate that nucleoporins have an active role in plant signaling.

Bogolubov–Hartree–Fock theory for strongly interacting fermions in the low density limit - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Mathematical Physics, Analysis and Geometry)
We consider the Bogolubov–Hartree–Fock functional for a fermionic many-body system with two-body interactions. For suitable interaction potentials that have a strong enough attractive tail in order to allow for two-body bound states, but are otherwise sufficiently repulsive to guarantee stability of the system, we show that in the low-density limit the ground state of this model consists of a Bose–Einstein condensate of fermion pairs. The latter can be described by means of the Gross–Pitaevskii energy functional.

The dual of the space of interactions in neural network models - De Martino, Daniele (International Journal of Modern Physics C)
In this work, the Gardner problem of inferring interactions and fields for an Ising neural network from given patterns under a local stability hypothesis is addressed under a dual perspective. By means of duality arguments, an integer linear system is defined whose solution space is the dual of the Gardner space and whose solutions represent mutually unstable patterns. We propose and discuss Monte Carlo methods in order to find and remove unstable patterns and uniformly sample the space of interactions thereafter. We illustrate the problem on a set of real data and perform ensemble calculation that shows how the emergence of phase dominated by unstable patterns can be triggered in a nonlinear discontinuous way.